Stability verification in stochastic control systems via neural network supermartingales - Lechner, Mathias; Zikelic, Dorde; Chatterjee, Krishnendu; Henzinger, Thomas A (Proceedings of the AAAI Conference on Artificial Intelligence)
We consider the problem of formally verifying almost-sure (a.s.) asymptotic stability in discrete-time nonlinear stochastic control systems. While verifying stability in deterministic control systems is extensively studied in the literature, verifying stability in stochastic control systems is an open problem. The few existing works on this topic either consider only specialized forms of stochasticity or make restrictive assumptions on the system, rendering them inapplicable to learning algorithms with neural network policies. In this work, we present an approach for general nonlinear stochastic control problems with two novel aspects: (a) instead of classical stochastic extensions of Lyapunov functions, we use ranking supermartingales (RSMs) to certify a.s. asymptotic stability, and (b) we present a method for learning neural network RSMs. We prove that our approach guarantees a.s. asymptotic stability of the system and provides the first method to obtain bounds on the stabilization time, which stochastic Lyapunov functions do not. Finally, we validate our approach experimentally on a set of nonlinear stochastic reinforcement learning environments with neural network policies.
Keywords: General Medicine

Learning stabilizing policies in stochastic control systems - Zikelic, Dorde; Lechner, Mathias; Chatterjee, Krishnendu; Henzinger, Thomas A (arXiv)
In this work, we address the problem of learning provably stable neural network policies for stochastic control systems. While recent work has demonstrated the feasibility of certifying given policies using martingale theory, the problem of how to learn such policies is little explored. Here, we study the effectiveness of jointly learning a policy together with a martingale certificate that proves its stability using a single learning algorithm. We observe that the joint optimization problem becomes easily stuck in local minima when starting from a randomly initialized policy. Our results suggest that some form of pre-training of the policy is required for the joint optimization to repair and verify the policy successfully.

Detecting induced p±ip pairing at the Al-InAs interface with a quantum microwave circuit - Phan, Duc T; Senior, Jorden L; Ghazaryan, Areg; Hatefipour, M.; Strickland, W. M.; Shabani, J.; Serbyn, Maksym; Higginbotham, Andrew P (Physical Review Letters)
Superconductor-semiconductor hybrid devices are at the heart of several proposed approaches to quantum information processing, but their basic properties remain to be understood. We embed a twodimensional Al-InAs hybrid system in a resonant microwave circuit, probing the breakdown of superconductivity due to an applied magnetic field. We find a fingerprint from the two-component nature of the hybrid system, and quantitatively compare with a theory that includes the contribution of intraband p±ip pairing in the InAs, as well as the emergence of Bogoliubov-Fermi surfaces due to magnetic field. Separately resolving the Al and InAs contributions allows us to determine the carrier density and mobility in the InAs.
Keywords: General Physics and Astronomy

An LC-MS/MS Assay for Enzymatic Characterization of Methylthioalkylmalate Synthase (MAMS) Involved in Glucosinolate Biosynthesis - Kumar, Roshan; Reichelt, Michael; Bisht, Naveen C. (Biochemical Pathways and Environmental Responses in Plants: Part A)
Brassicaceae are blessed with specialized metabolites called glucosinolates (GSLs), which along with their degradation products, are beneficial in agriculture and human health. To date, more than 130 GSL structures have been identified, mostly derived from the amino acid methionine. The biosynthesis of methionine-derived aliphatic GSLs starts with a side-chain elongation step involving a recursive three-step cyclic process that incorporates a new methylene group into the 2-oxo acid to form a series of elongated 2-oxo acids. Methylthioalkylmalate synthase (MAMS) catalyzes the first committed step in the side-chain elongation of methionine-derived GSLs. The substrate specificity of MAMS with different 2-oxo acids determines whether reaction products of a given cycle enter for an additional round of chain elongation or enter into core GSLs structure formation. Multiple MAMS encoding genes are present in the Brassicaceae species and are known to play a central role in shaping the diverse profile of aliphatic GSLs. We recently established a highly sensitive LC-MS/MS-based methodology that quantifies the MAMS activity by estimating the amount of the next intermediate of the pathway, the 2-malate derivatives. Overall, this chapter describes the protocol for the expression, purification, and steady-state kinetic analysis of the recombinant MAMS protein.

Avoiding barren plateaus using classical shadows - Sack, Stefan; Medina Ramos, Raimel A; Michailidis, Alexios; Kueng, Richard; Serbyn, Maksym (PRX Quantum)
Variational quantum algorithms are promising algorithms for achieving quantum advantage on nearterm devices. The quantum hardware is used to implement a variational wave function and measure observables, whereas the classical computer is used to store and update the variational parameters. The optimization landscape of expressive variational ansätze is however dominated by large regions in parameter space, known as barren plateaus, with vanishing gradients, which prevents efficient optimization. In this work we propose a general algorithm to avoid barren plateaus in the initialization and throughout the optimization. To this end we define a notion of weak barren plateaus (WBPs) based on the entropies of local reduced density matrices. The presence of WBPs can be efficiently quantified using recently introduced shadow tomography of the quantum state with a classical computer. We demonstrate that avoidance of WBPs suffices to ensure sizable gradients in the initialization. In addition, we demonstrate that decreasing the gradient step size, guided by the entropies allows WBPs to be avoided during the optimization process. This paves the way for efficient barren plateau-free optimization on near-term devices.
Keywords: General Medicine

Sharp asymptotics on the compression of two-layer neural networks - Amani, Mohammad Hossein; Bombari, Simone; Mondelli, Marco; Pukdee, Rattana; Rini, Stefano (IEEE Information Theory Workshop)
In this paper, we study the compression of a target two-layer neural network with N nodes into a compressed network with M<N nodes. More precisely, we consider the setting in which the weights of the target network are i.i.d. sub-Gaussian, and we minimize the population L_2 loss between the outputs of the target and of the compressed network, under the assumption of Gaussian inputs. By using tools from high-dimensional probability, we show that this non-convex problem can be simplified when the target network is sufficiently over-parameterized, and provide the error rate of this approximation as a function of the input dimension and N. In this mean-field limit, the simplified objective, as well as the optimal weights of the compressed network, does not depend on the realization of the target network, but only on expected scaling factors. Furthermore, for networks with ReLU activation, we conjecture that the optimum of the simplified optimization problem is achieved by taking weights on the Equiangular Tight Frame (ETF), while the scaling of the weights and the orientation of the ETF depend on the parameters of the target network. Numerical evidence is provided to support this conjecture.

Memorization and optimization in deep neural networks with minimum over-parameterization - Bombari, Simone; Amani, Mohammad Hossein; Mondelli, Marco (36th Conference on Neural Information Processing Systems)
The Neural Tangent Kernel (NTK) has emerged as a powerful tool to provide memorization, optimization and generalization guarantees in deep neural networks. A line of work has studied the NTK spectrum for two-layer and deep networks with at least a layer with Ω(N) neurons, N being the number of training samples. Furthermore, there is increasing evidence suggesting that deep networks with sub-linear layer widths are powerful memorizers and optimizers, as long as the number of parameters exceeds the number of samples. Thus, a natural open question is whether the NTK is well conditioned in such a challenging sub-linear setup. In this paper, we answer this question in the affirmative. Our key technical contribution is a lower bound on the smallest NTK eigenvalue for deep networks with the minimum possible over-parameterization: the number of parameters is roughly Ω(N) and, hence, the number of neurons is as little as Ω(N−−√). To showcase the applicability of our NTK bounds, we provide two results concerning memorization capacity and optimization guarantees for gradient descent training.

Plan your trip before you leave: The neutrophils’ search-and-run journey - Stopp, Julian A; Sixt, Michael K (Journal of Cell Biology)
Reading, interpreting and crawling along gradients of chemotactic cues is one of the most complex questions in cell biology. In this issue, Georgantzoglou et al. (2022. J. Cell. Biol.https://doi.org/10.1083/jcb.202103207) use in vivo models to map the temporal sequence of how neutrophils respond to an acutely arising gradient of chemoattractant.
Keywords: Cell Biology

Solid-state cooling: Thermoelectrics - Qin, Yongxin; Qin, Bingchao; Wang, Dongyang; Chang, Cheng; Zhao, Li-Dong (Energy & Environmental Science)
The growing demand of thermal management in various fields such as miniaturized 5G chips has motivated researchers to develop new and high-performance solid-state refrigeration technologies, typically including multicaloric and thermoelectric (TE) cooling. Among them, TE cooling has attracted huge attention owing to its advantages of rapid response, large cooling temperature difference, high stability, and tunable device size. Bi2Te3-based alloys have long been the only commercialized TE cooling materials, while novel systems SnSe and Mg3(Bi,Sb)2 have recently been discovered as potential candidates. However, challenges and problems still require to be summarized and further resolved for realizing better cooling performance. In this review, we systematically investigate TE cooling from its internal mechanism, crucial parameters, to device design and applications. Furthermore, we summarize the current optimization strategies for existing TE cooling materials, and finally provide some personal prospects especially the material-planification concept on future research on establishing better TE cooling.
Keywords: Pollution; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment; Environmental Chemistry

Learning control policies for stochastic systems with reach-avoid guarantees - Zikelic, Dorde; Lechner, Mathias; Henzinger, Thomas A; Chatterjee, Krishnendu (arXiv)
We study the problem of learning controllers for discrete-time non-linear stochastic dynamical systems with formal reach-avoid guarantees. This work presents the first method for providing formal reach-avoid guarantees, which combine and generalize stability and safety guarantees, with a tolerable probability threshold $p\in[0,1]$ over the infinite time horizon. Our method leverages advances in machine learning literature and it represents formal certificates as neural networks. In particular, we learn a certificate in the form of a reach-avoid supermartingale (RASM), a novel notion that we introduce in this work. Our RASMs provide reachability and avoidance guarantees by imposing constraints on what can be viewed as a stochastic extension of level sets of Lyapunov functions for deterministic systems. Our approach solves several important problems -- it can be used to learn a control policy from scratch, to verify a reach-avoid specification for a fixed control policy, or to fine-tune a pre-trained policy if it does not satisfy the reach-avoid specification. We validate our approach on $3$ stochastic non-linear reinforcement learning tasks.

ASIF: Coupled data turns unimodal models to multimodal without training - Norelli, Antonio; Fumero, Marco; Maiorca, Valentino; Moschella, Luca; Rodolà, Emanuele; Locatello, Francesco (arXiv)
CLIP proved that aligning visual and language spaces is key to solving many vision tasks without explicit training, but required to train image and text encoders from scratch on a huge dataset. LiT improved this by only training the text encoder and using a pre-trained vision network. In this paper, we show that a common space can be created without any training at all, using single-domain encoders (trained with or without supervision) and a much smaller amount of image-text pairs. Furthermore, our model has unique properties. Most notably, deploying a new version with updated training samples can be done in a matter of seconds. Additionally, the representations in the common space are easily interpretable as every dimension corresponds to the similarity of the input to a unique entry in the multimodal dataset. Experiments on standard zero-shot visual benchmarks demonstrate the typical transfer ability of image-text models. Overall, our method represents a simple yet surprisingly strong baseline for foundation multi-modal models, raising important questions on their data efficiency and on the role of retrieval in machine learning.

In vitro reconstitution of Escherichia coli divisome activation - Radler, Philipp
FtsA is crucial for assembly of the E. coli divisome, as it dynamically links cytoplasmic FtsZ filaments with transmembrane cell division proteins. FtsA allegedly initiates cell division by switching from an inactive polymeric to an active monomeric confirmation, which recruits downstream proteins and stabilizes FtsZ filaments. Here, we use biochemical reconstitution experiments combined with quantitative fluorescence microscopy to study divisome activation in vitro. We compare wildtype-FtsA with FtsA-R286W, a constantly active gain-of-function mutant and find that R286W outperforms the wildtype protein in replicating FtsZ treadmilling dynamics, stabilizing FtsZ filaments and recruiting FtsN. We attribute these differences to a faster membrane exchange of FtsA-R286W and its higher packing density below FtsZ filaments. Using FRET microscopy, we find that FtsN binding does not compete with, but promotes FtsA self-interaction. Our findings suggest a model where FtsA always forms dynamic polymers on the membrane, which re-organize during assembly and activation of the divisome.
Keywords: Bacterial cell division; in vitro reconstitution; FtsZ; FtsN; FtsA

In vitro reconstitution of Escherichia coli divisome activation - Radler, Philipp; Baranova, Natalia S.; Dos Santos Caldas, Paulo R; Sommer, Christoph M; Lopez Pelegrin, Maria D; Michalik, David; Loose, Martin (Nature Communications)
The actin-homologue FtsA is essential for E. coli cell division, as it links FtsZ filaments in the Z-ring to transmembrane proteins. FtsA is thought to initiate cell constriction by switching from an inactive polymeric to an active monomeric conformation, which recruits downstream proteins and stabilizes the Z-ring. However, direct biochemical evidence for this mechanism is missing. Here, we use reconstitution experiments and quantitative fluorescence microscopy to study divisome activation in vitro. By comparing wild-type FtsA with FtsA R286W, we find that this hyperactive mutant outperforms FtsA WT in replicating FtsZ treadmilling dynamics, FtsZ filament stabilization and recruitment of FtsN. We could attribute these differences to a faster exchange and denser packing of FtsA R286W below FtsZ filaments. Using FRET microscopy, we also find that FtsN binding promotes FtsA self-interaction. We propose that in the active divisome FtsA and FtsN exist as a dynamic copolymer that follows treadmilling filaments of FtsZ.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry

Chimeric GPCRs mimic distinct signaling pathways and modulate microglia responses - Schulz, Rouven; Korkut, Medina; Venturino, Alessandro; Colombo, Gloria; Siegert, Sandra (Nature Communications)
G protein-coupled receptors (GPCRs) regulate processes ranging from immune responses to neuronal signaling. However, ligands for many GPCRs remain unknown, suffer from off-target effects or have poor bioavailability. Additionally, dissecting cell type-specific responses is challenging when the same GPCR is expressed on different cells within a tissue. Here, we overcome these limitations by engineering DREADD-based GPCR chimeras that bind clozapine-N-oxide and mimic a GPCR-of-interest. We show that chimeric DREADD-β2AR triggers responses comparable to β2AR on second messenger and kinase activity, post-translational modifications, and protein-protein interactions. Moreover, we successfully recapitulate β2AR-mediated filopodia formation in microglia, an immune cell capable of driving central nervous system inflammation. When dissecting microglial inflammation, we included two additional DREADD-based chimeras mimicking microglia-enriched GPR65 and GPR109A. DREADD-β2AR and DREADD-GPR65 modulate the inflammatory response with high similarity to endogenous β2AR, while DREADD-GPR109A shows no impact. Our DREADD-based approach allows investigation of cell type-dependent pathways without known endogenous ligands.

Source Data (Chimeric GPCRs mimic distinct signaling pathways and modulate microglia responses) - Schulz, Rouven

Majorana-like Coulomb spectroscopy in the absence of zero-bias peaks - Valentini, Marco; Borovkov, Maksim; Prada, Elsa; Martí-Sánchez, Sara; Botifoll, Marc; Hofmann, Andrea C; Arbiol, Jordi; Aguado, Ramón; San-Jose, Pablo; Katsaros, Georgios (Nature)
Hybrid semiconductor–superconductor devices hold great promise for realizing topological quantum computing with Majorana zero modes1,2,3,4,5. However, multiple claims of Majorana detection, based on either tunnelling6,7,8,9,10 or Coulomb blockade (CB) spectroscopy11,12, remain disputed. Here we devise an experimental protocol that allows us to perform both types of measurement on the same hybrid island by adjusting its charging energy via tunable junctions to the normal leads. This method reduces ambiguities of Majorana detections by checking the consistency between CB spectroscopy and zero-bias peaks in non-blockaded transport. Specifically, we observe junction-dependent, even–odd modulated, single-electron CB peaks in InAs/Al hybrid nanowires without concomitant low-bias peaks in tunnelling spectroscopy. We provide a theoretical interpretation of the experimental observations in terms of low-energy, longitudinally confined island states rather than overlapping Majorana modes. Our results highlight the importance of combined measurements on the same device for the identification of topological Majorana zero modes.
Keywords: Multidisciplinary

Data for "Majorana-like Coulomb spectroscopy in the absence of zero bias peaks" - Valentini, Marco; San-Jose, Pablo; Arbiol, Jordi; Marti-Sanchez, Sara; Botifoll, Marc
This .zip File contains the transport data, the codes for the data analysis, the microscopy analysis and the codes for the theoretical simulations for "Majorana-like Coulomb spectroscopy in the absence of zero bias peaks" by M. Valentini, et. al. The transport data are saved with hdf5 file format. The files can be open with the log browser of Labber.

Effects of fine-scale population structure on the distribution of heterozygosity in a long-term study of Antirrhinum majus - Surendranadh, Parvathy; Arathoon, Louise S; Baskett, Carina; Field, David; Pickup, Melinda; Barton, Nicholas H (Genetics)
Many studies have quantified the distribution of heterozygosity and relatedness in natural populations, but few have examined the demographic processes driving these patterns. In this study, we take a novel approach by studying how population structure affects both pairwise identity and the distribution of heterozygosity in a natural population of the self-incompatible plant Antirrhinum majus. Excess variance in heterozygosity between individuals is due to identity disequilibrium, which reflects the variance in inbreeding between individuals; it is measured by the statistic g2. We calculated g2 together with FST and pairwise relatedness (Fij) using 91 SNPs in 22,353 individuals collected over 11 years. We find that pairwise Fij declines rapidly over short spatial scales, and the excess variance in heterozygosity between individuals reflects significant variation in inbreeding. Additionally, we detect an excess of individuals with around half the average heterozygosity, indicating either selfing or matings between close relatives. We use 2 types of simulation to ask whether variation in heterozygosity is consistent with fine-scale spatial population structure. First, by simulating offspring using parents drawn from a range of spatial scales, we show that the known pollen dispersal kernel explains g2. Second, we simulate a 1,000-generation pedigree using the known dispersal and spatial distribution and find that the resulting g2 is consistent with that observed from the field data. In contrast, a simulated population with uniform density underestimates g2, indicating that heterogeneous density promotes identity disequilibrium. Our study shows that heterogeneous density and leptokurtic dispersal can together explain the distribution of heterozygosity.

Effects of fine-scale population structure on the distribution of heterozygosity in a long-term study of Antirrhinum majus - Surendranadh, Parvathy; Arathoon, Louise S; Baskett, Carina; Field, David; Pickup, Melinda; Barton, Nicholas H
Here are the research data underlying the publication "Effects of fine-scale population structure on the distribution of heterozygosity in a long-term study of Antirrhinum majus" Further information are summed up in the README document.

When different norms lead to same billiard trajectories? - Akopyan, Arseniy; Karasev, Roman (European Journal of Mathematics)
Extending a result of Milena Radnovic and Serge Tabachnikov, we establish conditionsfor two different non-symmetric norms to define the same billiard reflection law.

Homogenizing yarn simulations: Large-scale mechanics, small-scale detail, and quantitative fitting - Sperl, Georg
The complex yarn structure of knitted and woven fabrics gives rise to both a mechanical and visual complexity. The small-scale interactions of yarns colliding with and pulling on each other result in drastically different large-scale stretching and bending behavior, introducing anisotropy, curling, and more. While simulating cloth as individual yarns can reproduce this complexity and match the quality of real fabric, it may be too computationally expensive for large fabrics. On the other hand, continuum-based approaches do not need to discretize the cloth at a stitch-level, but it is non-trivial to find a material model that would replicate the large-scale behavior of yarn fabrics, and they discard the intricate visual detail. In this thesis, we discuss three methods to try and bridge the gap between small-scale and large-scale yarn mechanics using numerical homogenization: fitting a continuum model to periodic yarn simulations, adding mechanics-aware yarn detail onto thin-shell simulations, and quantitatively fitting yarn parameters to physical measurements of real fabric. To start, we present a method for animating yarn-level cloth effects using a thin-shell solver. We first use a large number of periodic yarn-level simulations to build a model of the potential energy density of the cloth, and then use it to compute forces in a thin-shell simulator. The resulting simulations faithfully reproduce expected effects like the stiffening of woven fabrics and the highly deformable nature and anisotropy of knitted fabrics at a fraction of the cost of full yarn-level simulation. While our thin-shell simulations are able to capture large-scale yarn mechanics, they lack the rich visual detail of yarn-level simulations. Therefore, we propose a method to animate yarn-level cloth geometry on top of an underlying deforming mesh in a mechanics-aware fashion in real time. Using triangle strains to interpolate precomputed yarn geometry, we are able to reproduce effects such as knit loops tightening under stretching at negligible cost. Finally, we introduce a methodology for inverse-modeling of yarn-level mechanics of cloth, based on the mechanical response of fabrics in the real world. We compile a database from physical tests of several knitted fabrics used in the textile industry spanning diverse physical properties like stiffness, nonlinearity, and anisotropy. We then develop a system for approximating these mechanical responses with yarn-level cloth simulation, using homogenized shell models to speed up computation and adding some small-but-necessary extensions to yarn-level models used in computer graphics.

Analytic and machine learning approaches to composite quantum impurities - Rzadkowski, Wojciech
In this Thesis, I study composite quantum impurities with variational techniques, both inspired by machine learning as well as fully analytic. I supplement this with exploration of other applications of machine learning, in particular artificial neural networks, in many-body physics. In Chapters 3 and 4, I study quasiparticle systems with variational approach. I derive a Hamiltonian describing the angulon quasiparticle in the presence of a magnetic field. I apply analytic variational treatment to this Hamiltonian. Then, I introduce a variational approach for non-additive systems, based on artificial neural networks. I exemplify this approach on the example of the polaron quasiparticle (Fröhlich Hamiltonian). In Chapter 5, I continue using artificial neural networks, albeit in a different setting. I apply artificial neural networks to detect phases from snapshots of two types physical systems. Namely, I study Monte Carlo snapshots of multilayer classical spin models as well as molecular dynamics maps of colloidal systems. The main type of networks that I use here are convolutional neural networks, known for their applicability to image data.

Tetracycline-controlled (TetON) gene expression system for the smut fungus Ustilago maydis - Ingole, Kishor D.; Nagarajan, Nithya; Uhse, Simon; Giannini, Caterina; Djamei, Armin (Frontiers in Fungal Biology)
Ustilago maydis is a biotrophic phytopathogenic fungus that causes corn smut disease. As a well-established model system, U. maydis is genetically fully accessible with large omics datasets available and subject to various biological questions ranging from DNA-repair, RNA-transport, and protein secretion to disease biology. For many genetic approaches, tight control of transgene regulation is important. Here we established an optimised version of the Tetracycline-ON (TetON) system for U. maydis. We demonstrate the Tetracycline concentration-dependent expression of fluorescent protein transgenes and the system’s suitability for the induced expression of the toxic protein BCL2 Associated X-1 (Bax1). The Golden Gate compatible vector system contains a native minimal promoter from the mating factor a-1 encoding gene, mfa with ten copies of the tet-regulated operator (tetO) and a codon optimised Tet-repressor (tetR*) which is translationally fused to the native transcriptional corepressor Mql1 (UMAG_05501). The metabolism-independent transcriptional regulator system is functional both, in liquid culture as well as on solid media in the presence of the inducer and can become a useful tool for toxin-antitoxin studies, identification of antifungal proteins, and to study functions of toxic gene products in Ustilago maydis.

The effective mass problem for the Landau-Pekar equations - Feliciangeli, Dario; Rademacher, Simone Anna Elvira; Seiringer, Robert (Journal of Physics A: Mathematical and Theoretical)
We provide a definition of the effective mass for the classical polaron described by the Landau–Pekar (LP) equations. It is based on a novel variational principle, minimizing the energy functional over states with given (initial) velocity. The resulting formula for the polaron's effective mass agrees with the prediction by LP (1948 J. Exp. Theor. Phys. 18 419–423).

High capacity and dynamic accessibility in associative memory networks with context-dependent neuronal and synaptic gating - Podlaski, William F.; Agnes, Everton J.; Vogels, Tim P (bioRxiv)
Context, such as behavioral state, is known to modulate memory formation and retrieval, but is usually ignored in associative memory models. Here, we propose several types of contextual modulation for associative memory networks that greatly increase their performance. In these networks, context inactivates specific neurons and connections, which modulates the effective connectivity of the network. Memories are stored only by the active components, thereby reducing interference from memories acquired in other contexts. Such networks exhibit several beneficial characteristics, including enhanced memory capacity, high robustness to noise, increased robustness to memory overloading, and better memory retention during continual learning. Furthermore, memories can be biased to have different relative strengths, or even gated on or off, according to contextual cues, providing a candidate model for cognitive control of memory and efficient memory search. An external context-encoding network can dynamically switch the memory network to a desired state, which we liken to experimentally observed contextual signals in prefrontal cortex and hippocampus. Overall, our work illustrates the benefits of organizing memory around context, and provides an important link between behavioral studies of memory and mechanistic details of neural circuits. SIGNIFICANCE Memory is context dependent — both encoding and recall vary in effectiveness and speed depending on factors like location and brain state during a task. We apply this idea to a simple computational model of associative memory through contextual gating of neurons and synaptic connections. Intriguingly, this results in several advantages, including vastly enhanced memory capacity, better robustness, and flexible memory gating. Our model helps to explain (i) how gating and inhibition contribute to memory processes, (ii) how memory access dynamically changes over time, and (iii) how context representations, such as those observed in hippocampus and prefrontal cortex, may interact with and control memory processes.

Accumulation and maintenance of information in evolution - Hledik, Michal; Barton, Nicholas H; Tkačik, Gašper (Proceedings of the National Academy of Sciences)
Selection accumulates information in the genome—it guides stochastically evolving populations toward states (genotype frequencies) that would be unlikely under neutrality. This can be quantified as the Kullback–Leibler (KL) divergence between the actual distribution of genotype frequencies and the corresponding neutral distribution. First, we show that this population-level information sets an upper bound on the information at the level of genotype and phenotype, limiting how precisely they can be specified by selection. Next, we study how the accumulation and maintenance of information is limited by the cost of selection, measured as the genetic load or the relative fitness variance, both of which we connect to the control-theoretic KL cost of control. The information accumulation rate is upper bounded by the population size times the cost of selection. This bound is very general, and applies across models (Wright–Fisher, Moran, diffusion) and to arbitrary forms of selection, mutation, and recombination. Finally, the cost of maintaining information depends on how it is encoded: Specifying a single allele out of two is expensive, but one bit encoded among many weakly specified loci (as in a polygenic trait) is cheap.

Approximate message passing with spectral initialization for generalized linear models - Mondelli, Marco; Venkataramanan, Ramji (Journal of Statistical Mechanics: Theory and Experiment)
We consider the problem of estimating a signal from measurements obtained via a generalized linear model. We focus on estimators based on approximate message passing (AMP), a family of iterative algorithms with many appealing features: the performance of AMP in the high-dimensional limit can be succinctly characterized under suitable model assumptions; AMP can also be tailored to the empirical distribution of the signal entries, and for a wide class of estimation problems, AMP is conjectured to be optimal among all polynomial-time algorithms. However, a major issue of AMP is that in many models (such as phase retrieval), it requires an initialization correlated with the ground-truth signal and independent from the measurement matrix. Assuming that such an initialization is available is typically not realistic. In this paper, we solve this problem by proposing an AMP algorithm initialized with a spectral estimator. With such an initialization, the standard AMP analysis fails since the spectral estimator depends in a complicated way on the design matrix. Our main contribution is a rigorous characterization of the performance of AMP with spectral initialization in the high-dimensional limit. The key technical idea is to define and analyze a two-phase artificial AMP algorithm that first produces the spectral estimator, and then closely approximates the iterates of the true AMP. We also provide numerical results that demonstrate the validity of the proposed approach.
Keywords: Statistics; Probability and Uncertainty; Statistics and Probability; Statistical and Nonlinear Physics

A window to the persistence of 1D maps. I: Geometric characterization of critical point pairs - Biswas, Ranita; Cultrera di Montesano, Sebastiano; Edelsbrunner, Herbert; Saghafian, Morteza (LIPIcs)
We characterize critical points of 1-dimensional maps paired in persistent homology geometrically and this way get elementary proofs of theorems about the symmetry of persistence diagrams and the variation of such maps. In particular, we identify branching points and endpoints of networks as the sole source of asymmetry and relate the cycle basis in persistent homology with a version of the stable marriage problem. Our analysis provides the foundations of fast algorithms for maintaining collections of interrelated sorted lists together with their persistence diagrams.

On the size of chromatic Delaunay mosaics - Biswas, Ranita; Cultrera di Montesano, Sebastiano; Draganov, Ondrej; Edelsbrunner, Herbert; Saghafian, Morteza (arXiv)
Given a locally finite set A⊆Rd and a coloring χ:A→{0,1,…,s}, we introduce the chromatic Delaunay mosaic of χ, which is a Delaunay mosaic in Rs+d that represents how points of different colors mingle. Our main results are bounds on the size of the chromatic Delaunay mosaic, in which we assume that d and s are constants. For example, if A is finite with n=#A, and the coloring is random, then the chromatic Delaunay mosaic has O(n⌈d/2⌉) cells in expectation. In contrast, for Delone sets and Poisson point processes in Rd, the expected number of cells within a closed ball is only a constant times the number of points in this ball. Furthermore, in R2 all colorings of a dense set of n points have chromatic Delaunay mosaics of size O(n). This encourages the use of chromatic Delaunay mosaics in applications.

Weak-strong uniqueness for the Navier–Stokes equation for two fluids with ninety degree contact angle and same viscosities - Hensel, Sebastian; Marveggio, Alice (Journal of Mathematical Fluid Mechanics)
We consider the flow of two viscous and incompressible fluids within a bounded domain modeled by means of a two-phase Navier–Stokes system. The two fluids are assumed to be immiscible, meaning that they are separated by an interface. With respect to the motion of the interface, we consider pure transport by the fluid flow. Along the boundary of the domain, a complete slip boundary condition for the fluid velocities and a constant ninety degree contact angle condition for the interface are assumed. In the present work, we devise for the resulting evolution problem a suitable weak solution concept based on the framework of varifolds and establish as the main result a weak-strong uniqueness principle in 2D. The proof is based on a relative entropy argument and requires a non-trivial further development of ideas from the recent work of Fischer and the first author (Arch. Ration. Mech. Anal. 236, 2020) to incorporate the contact angle condition. To focus on the effects of the necessarily singular geometry of the evolving fluid domains, we work for simplicity in the regime of same viscosities for the two fluids.

Quantitative convergence of the vectorial Allen-Cahn equation towards multiphase mean curvature flow - Fischer, Julian L; Marveggio, Alice (arXiv)
Phase-field models such as the Allen-Cahn equation may give rise to the formation and evolution of geometric shapes, a phenomenon that may be analyzed rigorously in suitable scaling regimes. In its sharp-interface limit, the vectorial Allen-Cahn equation with a potential with N≥3 distinct minima has been conjectured to describe the evolution of branched interfaces by multiphase mean curvature flow. In the present work, we give a rigorous proof for this statement in two and three ambient dimensions and for a suitable class of potentials: As long as a strong solution to multiphase mean curvature flow exists, solutions to the vectorial Allen-Cahn equation with well-prepared initial data converge towards multiphase mean curvature flow in the limit of vanishing interface width parameter ε↘0. We even establish the rate of convergence O(ε1/2). Our approach is based on the gradient flow structure of the Allen-Cahn equation and its limiting motion: Building on the recent concept of "gradient flow calibrations" for multiphase mean curvature flow, we introduce a notion of relative entropy for the vectorial Allen-Cahn equation with multi-well potential. This enables us to overcome the limitations of other approaches, e.g. avoiding the need for a stability analysis of the Allen-Cahn operator or additional convergence hypotheses for the energy at positive times.

The x-ray polarimetry view of the accreting pulsar Cen X-3 - Tsygankov, Sergey S.; Doroshenko, Victor; Poutanen, Juri; Heyl, Jeremy; Mushtukov, Alexander A.; Caiazzo, Ilaria; Di Marco, Alessandro; Forsblom, Sofia V.; González-Caniulef, Denis; Klawin, Moritz; La Monaca, Fabio; Malacaria, Christian; et al. (The Astrophysical Journal Letters)
The first X-ray pulsar, Cen X-3, was discovered 50 yr ago. Radiation from such objects is expected to be highly polarized due to birefringence of plasma and vacuum associated with propagation of photons in the presence of the strong magnetic field. Here we present results of the observations of Cen X-3 performed with the Imaging X-ray Polarimetry Explorer. The source exhibited significant flux variability and was observed in two states different by a factor of ∼20 in flux. In the low-luminosity state, no significant polarization was found in either pulse phase-averaged (with a 3σ upper limit of 12%) or phase-resolved (the 3σ upper limits are 20%–30%) data. In the bright state, the polarization degree of 5.8% ± 0.3% and polarization angle of 49fdg6 ± 1fdg5 with a significance of about 20σ were measured from the spectropolarimetric analysis of the phase-averaged data. The phase-resolved analysis showed a significant anticorrelation between the flux and the polarization degree, as well as strong variations of the polarization angle. The fit with the rotating vector model indicates a position angle of the pulsar spin axis of about 49° and a magnetic obliquity of 17°. The detected relatively low polarization can be explained if the upper layers of the neutron star surface are overheated by the accreted matter and the conversion of the polarization modes occurs within the transition region between the upper hot layer and a cooler underlying atmosphere. A fraction of polarization signal can also be produced by reflection of radiation from the neutron star surface and the accretion curtain.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Polarized x-rays from a magnetar - Taverna, Roberto; Turolla, Roberto; Muleri, Fabio; Heyl, Jeremy; Zane, Silvia; Baldini, Luca; González-Caniulef, Denis; Bachetti, Matteo; Rankin, John; Caiazzo, Ilaria; Di Lalla, Niccolò; Doroshenko, Victor; et al. (Science)
Magnetars are neutron stars with ultrastrong magnetic fields, which can be observed in x-rays. Polarization measurements could provide information on their magnetic fields and surface properties. We observed polarized x-rays from the magnetar 4U 0142+61 using the Imaging X-ray Polarimetry Explorer and found a linear polarization degree of 13.5 ± 0.8% averaged over the 2– to 8–kilo–electron volt band. The polarization changes with energy: The degree is 15.0 ± 1.0% at 2 to 4 kilo–electron volts, drops below the instrumental sensitivity ~4 to 5 kilo–electron volts, and rises to 35.2 ± 7.1% at 5.5 to 8 kilo–electron volts. The polarization angle also changes by 90° at ~4 to 5 kilo–electron volts. These results are consistent with a model in which thermal radiation from the magnetar surface is reprocessed by scattering off charged particles in the magnetosphere.
Keywords: Multidisciplinary

Determination of X-ray pulsar geometry with IXPE polarimetry - Doroshenko, Victor; Poutanen, Juri; Tsygankov, Sergey S.; Suleimanov, Valery F.; Bachetti, Matteo; Caiazzo, Ilaria; Costa, Enrico; Di Marco, Alessandro; Heyl, Jeremy; La Monaca, Fabio; Muleri, Fabio; Mushtukov, Alexander A.; et al. (Nature Astronomy)
Using observations of X-ray pulsar Hercules X-1 by the Imaging X-ray Polarimetry Explorer we report a highly significant (>17σ) detection of the polarization signal from an accreting neutron star. The observed degree of linear polarization of ~10% is far below theoretical expectations for this object, and stays low throughout the spin cycle of the pulsar. Both the degree and angle of polarization exhibit variability with the pulse phase, allowing us to measure the pulsar spin position angle 57(2) deg and the magnetic obliquity 12(4) deg, which is an essential step towards detailed modelling of the intrinsic emission of X-ray pulsars. Combining our results with the optical polarimetric data, we find that the spin axis of the neutron star and the angular momentum of the binary orbit are misaligned by at least ~20 deg, which is a strong argument in support of the models explaining the stability of the observed superorbital variability with the precession of the neutron star.
Keywords: Astronomy and Astrophysics

A dense 0.1-solar-mass star in a 51-minute-orbital-period eclipsing binary - Burdge, Kevin B.; El-Badry, Kareem; Marsh, Thomas R.; Rappaport, Saul; Brown, Warren R.; Caiazzo, Ilaria; Chakrabarty, Deepto; Dhillon, V. S.; Fuller, Jim; Gänsicke, Boris T.; Graham, Matthew J.; Kara, Erin; et al. (Nature)
Of more than a thousand known cataclysmic variables (CVs), where a white dwarf is accreting from a hydrogen-rich star, only a dozen have orbital periods below 75 minutes1,2,3,4,5,6,7,8,9. One way to achieve these short periods requires the donor star to have undergone substantial nuclear evolution before interacting with the white dwarf10,11,12,13,14, and it is expected that these objects will transition to helium accretion. These transitional CVs have been proposed as progenitors of helium CVs13,14,15,16,17,18. However, no known transitional CV is expected to reach an orbital period short enough to account for most of the helium CV population, leaving the role of this evolutionary pathway unclear. Here we report observations of ZTF J1813+4251, a 51-minute-orbital-period, fully eclipsing binary system consisting of a star with a temperature comparable to that of the Sun but a density 100 times greater owing to its helium-rich composition, accreting onto a white dwarf. Phase-resolved spectra, multi-band light curves and the broadband spectral energy distribution allow us to obtain precise and robust constraints on the masses, radii and temperatures of both components. Evolutionary modelling shows that ZTF J1813+4251 is destined to become a helium CV binary, reaching an orbital period under 20 minutes, rendering ZTF J1813+4251 a previously missing link between helium CV binaries and hydrogen-rich CVs.

Probing magnetar emission mechanisms with X-ray spectropolarimetry - Caiazzo, Ilaria; González-Caniulef, Denis; Heyl, Jeremy; Fernández, Rodrigo (Monthly Notices of the Royal Astronomical Society)
This year, a new era of observations of compact objects in X-ray polarization is commencing. Among the key targets for the Imaging X-ray Polarimetry Explorer mission are the magnetars 4U 0142+61 and 1RXS J170849.0-400910. Here, we present detailed predictions of the expected polarization from these sources that incorporate realistic models of emission physics at the surface (gaseous or condensed), the temperature distribution on the surface, general relativity, quantum electrodynamics, and scattering in the magnetosphere, accounting for the broad-band spectral energy distribution from below 1 keV to nearly 100 keV. We find that either atmospheres or condensed surfaces can account for the emission at a few keV. In both cases, either a small hot polar cap or scattering is required to account for the emission at 5–10 keV and, above 10 keV, scattering by a hard population of electrons can account for the rising power in the hard X-rays observed in many magnetars in quiescence. Although these different scenarios result in very similar spectral energy distributions, they generate dramatically different polarization signatures from 2 to 8 keV, which is the range of sensitivity of the Imaging X-ray Polarimetry Explorer. Observations of these sources in X-ray polarization will therefore probe the emission from magnetars in an essentially new way.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Testing general relativity using quasi-periodic oscillations from X-ray black holes: XTE J1550-564 and GRO J1655-40 - Rink, Katherine; Caiazzo, Ilaria; Heyl, Jeremy (Monthly Notices of the Royal Astronomical Society)
We use the Relativistic Precession Model (RPM) and quasi-periodic oscillation (QPO) observations from the Rossi X-ray Timing Explorer to derive constraints on the properties of the black holes that power these sources and to test general relativity (GR) in the strong field regime. We build upon past techniques by using pairs of simultaneously measured QPOs, rather than triplets, and by including characteristic frequencies from the broad noise components of the power spectra in our fits. We find the inclusion of these broad noise components causes an overestimate in masses and underestimate in spins compared to values derived independently from optical spectra. We extend the underlying space-time metric to constrain potential deviations from the predictions of GR for astrophysical black holes. To do this, we modify the RPM model to a Kerr–Newman–deSitter space-time and model changes in the radial, ecliptic, and vertical frequencies. We compare our models with X-ray data of XTE J1550-564 and GRO J1655-40 using robust statistical techniques to constrain the parameters of the black holes and the deviations from GR. For both sources, using QPO and characteristic frequency data, we constrain particular deviations from GR to be less than one part per thousand.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

A 62-minute orbital period black widow binary in a wide hierarchical triple - Burdge, Kevin B.; Marsh, Thomas R.; Fuller, Jim; Bellm, Eric C.; Caiazzo, Ilaria; Chakrabarty, Deepto; Coughlin, Michael W.; De, Kishalay; Dhillon, V. S.; Graham, Matthew J.; Rodríguez-Gil, Pablo; Jaodand, Amruta D.; et al. (Nature)
Over a dozen millisecond pulsars are ablating low-mass companions in close binary systems. In the original ‘black widow’, the eight-hour orbital period eclipsing pulsar PSR J1959+2048 (PSR B1957+20)1, high-energy emission originating from the pulsar2 is irradiating and may eventually destroy3 a low-mass companion. These systems are not only physical laboratories that reveal the interesting results of exposing a close companion star to the relativistic energy output of a pulsar, but are also believed to harbour some of the most massive neutron stars4, allowing for robust tests of the neutron star equation of state. Here we report observations of ZTF J1406+1222, a wide hierarchical triple hosting a 62-minute orbital period black widow candidate, the optical flux of which varies by a factor of more than ten. ZTF J1406+1222 pushes the boundaries of evolutionary models5, falling below the 80-minute minimum orbital period of hydrogen-rich systems. The wide tertiary companion is a rare low-metallicity cool subdwarf star, and the system has a Galactic halo orbit consistent with passing near the Galactic Centre, making it a probe of formation channels, neutron star kick physics6 and binary evolution.
Keywords: Multidisciplinary

When do stars go boom? - Richer, Harvey B.; Cohen, Roger E.; Heyl, Jeremy; Kalirai, Jason; Caiazzo, Ilaria; Correnti, Matteo; Cummings, Jeffrey; Goudfrooij, Paul; Hansen, Bradley M. S.; Peeples, Molly; Sabbi, Elena; Tremblay, Pier-Emmanuel; et al. (The Astrophysical Journal Letters)
The maximum mass of a star that can produce a white dwarf (WD) is an important astrophysical quantity. One of the best approaches to establishing this limit is to search for WDs in young star clusters in which only massive stars have had time to evolve and where the mass of the progenitor can be established from the cooling time of the WD together with the age of the cluster. Searches in young Milky Way clusters have not thus far yielded WD members more massive than about 1.1 M⊙, well below the Chandrasekhar mass of 1.38 M⊙, nor progenitors with masses in excess of about 6 M⊙. However, the hunt for potentially massive WDs that escaped their cluster environs is yielding interesting candidates. To expand the cluster sample further, we used HST to survey four young and massive star clusters in the Magellanic Clouds for bright WDs that could have evolved from stars as massive as 10 M⊙. We located five potential WD candidates in the oldest of the four clusters examined, the first extragalactic single WDs thus far discovered. As these hot WDs are very faint at optical wavelengths, final confirmation will likely have to await spectroscopy with 30 m class telescopes.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Slow convection and fast rotation in crystallization-driven white dwarf dynamos - Ginzburg, Sivan; Fuller, Jim; Kawka, Adela; Caiazzo, Ilaria (Monthly Notices of the Royal Astronomical Society)
It has been recently suggested that white dwarfs generate magnetic fields in a process analogous to the Earth. The crystallization of the core creates a compositional inversion that drives convection, and combined with rotation, this can sustain a magnetic dynamo. We reanalyse the dynamo mechanism, arising from the slow crystallization of the core, and find convective turnover times tconv of weeks to months – longer by orders of magnitude than previously thought. With white dwarf spin periods P ≪ tconv, crystallization-driven dynamos are almost always in the fast-rotating regime, where the magnetic field B is at least in equipartition with the convective motion and is possibly further enhanced by a factor of B ∝ (tconv/P)1/2, depending on the assumed dynamo scaling law. We track the growth of the crystallized core using MESA and compute the magnetic field B(Teff) as a function of the white dwarf’s effective temperature Teff. We compare this prediction with observations and show that crystallization-driven dynamos can explain some – but not all – of the ∼MG magnetic fields measured for single white dwarfs, as well as the stronger fields measured for white dwarfs in cataclysmic variables, which were spun up by mass accretion to short P. Our B(Teff) curves might also explain the clustering of white dwarfs with Balmer emission lines around Teff ≈ 7500 K.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

The cooling of massive white dwarfs from Gaia EDR3 - Fleury, Leesa; Caiazzo, Ilaria; Heyl, Jeremy (Monthly Notices of the Royal Astronomical Society)
We determine the distribution of cooling ages of massive Gaia EDR3 white dwarfs identified with over 90 per cent probability within 200 pc and with mass in the range 0.95–1.25 M⊙. Using three sets of publicly available models, we consider sub-samples of these white dwarfs sorted into three equally spaced mass bins. Under the assumption of a constant white dwarf formation rate, we find an excess of white dwarfs, both along the Q branch and below it, corresponding respectively to stars that are in the process of freezing and those that are completely frozen. We compare the cooling age distributions for each of these bins to the recently determined time-varying star formation rate of Gaia DR2 main sequence stars. For white dwarfs in the two lightest mass bins, spanning the mass range 0.95–1.15 M⊙, we find that the cumulative cooling age distribution is statistically consistent with the expectation from the star formation rate. For white dwarfs in the heaviest mass bin, 1.15–1.25 M⊙, we find that their cumulative distribution is inconsistent with the star formation rate for all of the models considered; instead, we find that their cooling age distribution is well fitted by a linear combination of the distribution expected for single stellar evolution products and the distribution expected for double white dwarf merger products when approximately 40–50 per cent of the 1.15–1.25 M⊙ white dwarfs that formed over the past 4 Gyr are produced through double white dwarf mergers.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

The ultramassive white dwarfs of the Alpha Persei cluster - Miller, David R.; Caiazzo, Ilaria; Heyl, Jeremy; Richer, Harvey B.; Tremblay, Pier-Emmanuel (The Astrophysical Journal Letters)
We searched through the entire Gaia EDR3 candidate white dwarf catalog for stars with proper motions and positions that are consistent with them having escaped from the Alpha Persei cluster within the past 81 Myr, the age of the cluster. In this search we found five candidate white dwarf escapees from Alpha Persei and obtained spectra for all of them. We confirm that three are massive white dwarfs sufficiently young to have originated in the cluster. All these are more massive than any white dwarf previously associated with a cluster using Gaia astrometry, and possess some of the most massive progenitors. In particular, the white dwarf Gaia EDR3 4395978097863572, which lies within 25 pc of the cluster center, has a mass of about 1.20 solar masses and evolved from an 8.5 solar-mass star, pushing the upper limit for white dwarf formation from a single massive star, while still leaving a substantial gap between the resulting white dwarf mass and the Chandrasekhar mass.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Reconstructing the Pleiades with Gaia EDR3 - Heyl, Jeremy; Caiazzo, Ilaria; Richer, Harvey B. (The Astrophysical Journal)
We search through an eight million cubic parsec volume surrounding the Pleiades star cluster and the Sun to identify both the current and past members of the Pleiades cluster within the Gaia EDR3 data set. We find nearly 1300 current cluster members and 289 former cluster candidates. Many of these candidates lie well in front of or behind the cluster from our point of view, so formerly they were considered cluster members, but their parallaxes put them more than 10 pc from the center of the cluster today. Over the past 100 Myr we estimate that the cluster has lost twenty percent of its mass including two massive white dwarf stars and the α2 Canum Venaticorum type variable star, 41 Tau. All three white dwarfs associated with the cluster are massive (1.01–1.06 M⊙) and have progenitors with main-sequence masses of about six solar masses. Although we did not associate any giant stars with the cluster, the cooling time of the oldest white dwarf of 60 Myr gives a firm lower limit on the age of the cluster.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

SuperFi-Cas9 exceeds fidelity, matches speed of original Cas9 - Bravo, Jack Peter Kelly (Genetic Engineering & Biotechnology News)
Keywords: Management of Technology and Innovation; Biomedical Engineering; Bioengineering; Biotechnology

The response of a metapopulation to a changing environment - Barton, Nicholas H; Olusanya, Oluwafunmilola O (Philosophical Transactions of the Royal Society B: Biological Sciences)
A species distributed across diverse environments may adapt to local conditions. We ask how quickly such a species changes its range in response to changed conditions. Szép et al. (Szép E, Sachdeva H, Barton NH. 2021 Polygenic local adaptation in metapopulations: a stochastic eco-evolutionary model. Evolution75, 1030–1045 (doi:10.1111/evo.14210)) used the infinite island model to find the stationary distribution of allele frequencies and deme sizes. We extend this to find how a metapopulation responds to changes in carrying capacity, selection strength, or migration rate when deme sizes are fixed. We further develop a ‘fixed-state’ approximation. Under this approximation, polymorphism is only possible for a narrow range of habitat proportions when selection is weak compared to drift, but for a much wider range otherwise. When rates of selection or migration relative to drift change in a single deme of the metapopulation, the population takes a time of order m−1 to reach the new equilibrium. However, even with many loci, there can be substantial fluctuations in net adaptation, because at each locus, alleles randomly get lost or fixed. Thus, in a finite metapopulation, variation may gradually be lost by chance, even if it would persist in an infinite metapopulation. When conditions change across the whole metapopulation, there can be rapid change, which is predicted well by the fixed-state approximation. This work helps towards an understanding of how metapopulations extend their range across diverse environments. This article is part of the theme issue ‘Species’ ranges in the face of changing environments (Part II)’.
Keywords: General Agricultural and Biological Sciences; General Biochemistry; Genetics and Molecular Biology

Genetic load and extinction in peripheral populations: The roles of migration, drift and demographic stochasticity - Sachdeva, Himani; Olusanya, Oluwafunmilola O; Barton, Nicholas H (Philosophical Transactions of the Royal Society B)
We analyse how migration from a large mainland influences genetic load and population numbers on an island, in a scenario where fitness-affecting variants are unconditionally deleterious, and where numbers decline with increasing load. Our analysis shows that migration can have qualitatively different effects, depending on the total mutation target and fitness effects of deleterious variants. In particular, we find that populations exhibit a genetic Allee effect across a wide range of parameter combinations, when variants are partially recessive, cycling between low-load (large-population) and high-load (sink) states. Increased migration reduces load in the sink state (by increasing heterozygosity) but further inflates load in the large-population state (by hindering purging). We identify various critical parameter thresholds at which one or other stable state collapses, and discuss how these thresholds are influenced by the genetic versus demographic effects of migration. Our analysis is based on a ‘semi-deterministic’ analysis, which accounts for genetic drift but neglects demographic stochasticity. We also compare against simulations which account for both demographic stochasticity and drift. Our results clarify the importance of gene flow as a key determinant of extinction risk in peripheral populations, even in the absence of ecological gradients. This article is part of the theme issue ‘Species’ ranges in the face of changing environments (part I)’.

Remodeling of E-cadherin-mediated contacts via cortical flows - Arslan, Feyza N
Metazoan development relies on the formation and remodeling of cell-cell contacts. The binding of adhesion receptors and remodeling of the actomyosin cell cortex at cell-cell interaction sites have been implicated in cell-cell contact formation. Yet, how these two processes functionally interact to drive cell-cell contact expansion and strengthening remains unclear. Here, we study how primary germ layer progenitor cells from zebrafish bind to supported lipid bilayers (SLB) functionalized with E-cadherin ectodomains as an assay system for monitoring cell-cell contact formation at high spatiotemporal resolution. We show that cell-cell contact formation represents a two-tiered process: E-cadherinmediated downregulation of the small GTPase RhoA at the forming contact leads to both depletion of Myosin-2 and decrease of F-actin. This is followed by centrifugal actin network flows at the contact triggered by a sharp gradient of Myosin-2 at the rim of the contact zone, with Myosin-2 displaying higher cortical localization outside than inside of the contact. These centrifugal cortical actin flows, in turn, not only further dilute the actin network at the contact disc, but also lead to an accumulation of both F-actin and Ecadherin at the contact rim. Eventually, this combination of actomyosin downregulation and flows at the contact contribute to the characteristic molecular organization implicated in contact formation and maintenance: depletion of cortical actomyosin at the contact disc, driving contact expansion by lowering interfacial tension at the contact, and accumulation of both E-cadherin and F-actin at the contact rim, mechanically linking the contractile cortices of the adhering cells. Thus, using a biomimetic assay, we exemplify how adhesion signaling and cell mechanics function together to modulate the spatial organization of cell-cell contacts.

Evolutionary and structural constraints influencing apolipoprotein A‐I amyloid behavior - Gisonno, Romina A.; Masson, Tomas; Ramella, Nahuel A.; Barrera, Exequiel E.; Romanowski, Víctor; Tricerri, M. Alejandra (Proteins: Structure, Function, and Bioinformatics)
Apolipoprotein A‐I (apoA‐I) has a key function in the reverse cholesterol transport. However, aggregation of apoA‐I single point mutants can lead to hereditary amyloid pathology. Although several studies have tackled the biophysical and structural consequences introduced by these mutations, there is little information addressing the relationship between the evolutionary and structural features that contribute to the amyloid behavior of apoA‐I. We combined evolutionary studies, in silico mutagenesis and molecular dynamics (MD) simulations to provide a comprehensive analysis of the conservation and pathogenic role of the aggregation‐prone regions (APRs) present in apoA‐I. Sequence analysis demonstrated that among the four amyloidogenic regions described for human apoA‐I, only two (APR1 and APR4) are evolutionary conserved across different species of Sarcopterygii. Moreover, stability analysis carried out with the FoldX engine showed that APR1 contributes to the marginal stability of apoA‐I. Structural properties of full‐length apoA‐I models suggest that aggregation is avoided by placing APRs into highly packed and rigid portions of its native fold. Compared to silent variants extracted from the gnomAD database, the thermodynamic and pathogenic impact of amyloid mutations showed evidence of a higher destabilizing effect. MD simulations of the amyloid variant G26R evidenced the partial unfolding of the alpha‐helix bundle with the concomitant exposure of APR1 to the solvent, suggesting an insight into the early steps involved in its aggregation. Our findings highlight APR1 as a relevant component for apoA‐I structural integrity and emphasize a destabilizing effect of amyloid variants that leads to the exposure of this region.
Keywords: Molecular Biology; Biochemistry; Structural Biology

Depth in arrangements: Dehn–Sommerville–Euler relations with applications - Biswas, Ranita; Cultrera di Montesano, Sebastiano; Edelsbrunner, Herbert; Saghafian, Morteza (Leibniz International Proceedings on Mathematics)
The depth of a cell in an arrangement of n (non-vertical) great-spheres in Sd is the number of great-spheres that pass above the cell. We prove Euler-type relations, which imply extensions of the classic Dehn–Sommerville relations for convex polytopes to sublevel sets of the depth function, and we use the relations to extend the expressions for the number of faces of neighborly polytopes to the number of cells of levels in neighborly arrangements.

Solution-processed inorganic thermoelectric materials: Opportunities and challenges ∇ - Fiedler, Christine; Kleinhanns, Tobias; Garcia, Maria; Lee, Seungho; Calcabrini, Mariano; Ibáñez, Maria (Chemistry of Materials)
Thermoelectric technology requires synthesizing complex materials where not only the crystal structure but also other structural features such as defects, grain size and orientation, and interfaces must be controlled. To date, conventional solid-state techniques are unable to provide this level of control. Herein, we present a synthetic approach in which dense inorganic thermoelectric materials are produced by the consolidation of well-defined nanoparticle powders. The idea is that controlling the characteristics of the powder allows the chemical transformations that take place during consolidation to be guided, ultimately yielding inorganic solids with targeted features. Different from conventional methods, syntheses in solution can produce particles with unprecedented control over their size, shape, crystal structure, composition, and surface chemistry. However, to date, most works have focused only on the low-cost benefits of this strategy. In this perspective, we first cover the opportunities that solution processing of the powder offers, emphasizing the potential structural features that can be controlled by precisely engineering the inorganic core of the particle, the surface, and the organization of the particles before consolidation. We then discuss the challenges of this synthetic approach and more practical matters related to solution processing. Finally, we suggest some good practices for adequate knowledge transfer and improving reproducibility among different laboratories.
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

Nanoarchitecture of hippocampal mossy fiber-CA3 pyramidal neuron synapses - Kim, Olena
One of the fundamental questions in Neuroscience is how the structure of synapses and their physiological properties are related. While synaptic transmission remains a dynamic process, electron microscopy provides images with comparably low temporal resolution (Studer et al., 2014). The current work overcomes this challenge and describes an improved “Flash and Freeze” technique (Watanabe et al., 2013a; Watanabe et al., 2013b) to study synaptic transmission at the hippocampal mossy fiber-CA3 pyramidal neuron synapses, using mouse acute brain slices and organotypic slices culture. The improved method allowed for selective stimulation of presynaptic mossy fiber boutons and the observation of synaptic vesicle pool dynamics at the active zones. Our results uncovered several intriguing morphological features of mossy fiber boutons. First, the docked vesicle pool was largely depleted (more than 70%) after stimulation, implying that the docked synaptic vesicles pool and readily releasable pool are vastly overlapping in mossy fiber boutons. Second, the synaptic vesicles are skewed towards larger diameters, displaying a wide range of sizes. An increase in the mean diameter of synaptic vesicles, after single and repetitive stimulation, suggests that smaller vesicles have a higher release probability. Third, we observed putative endocytotic structures after moderate light stimulation, matching the timing of previously described ultrafast endocytosis (Watanabe et al., 2013a; Delvendahl et al., 2016). In addition, synaptic transmission depends on a sophisticated system of protein machinery and calcium channels (Südhof, 2013b), which amplifies the challenge in studying synaptic communication as these interactions can be potentially modified during synaptic plasticity. And although recent study elucidated the potential correlation between physiological and morphological properties of synapses during synaptic plasticity (Vandael et al., 2020), the molecular underpinning of it remains unknown. Thus, the presented work tries to overcome this challenge and aims to pinpoint changes in the molecular architecture at hippocampal mossy fiber bouton synapses during short- and long-term potentiation (STP and LTP), we combined chemical potentiation, with the application of a cyclic adenosine monophosphate agonist (i.e. forskolin) and freeze-fracture replica immunolabelling. This method allowed the localization of membrane-bound proteins with nanometer precision within the active zone, in particular, P/Q-type calcium channels and synaptic vesicle priming proteins Munc13-1/2. First, we found that the number of clusters of Munc13-1 in the mossy fiber bouton active zone increased significantly during STP, but decreased to lower than the control value during LTP. Secondly, although the distance between the calcium channels and Munc13-1s did not change after induction of STP, it shortened during the LTP phase. Additionally, forskolin did not affect Munc13-2 distribution during STP and LTP. These results indicate the existence of two distinct mechanisms that govern STP and LTP at mossy fiber bouton synapses: an increase in the readily realizable pool in the case of STP and a potential increase in release probability during LTP. “Flash and freeze” and functional electron microscopy, are versatile methods that can be successfully applied to intact brain circuits to study synaptic transmission even at the molecular level.

Pathogen-mediated sexual selection and immunization in ant colonies - Metzler, Sina
Social insects are a common model to study disease dynamics in social animals. Even though pathogens should thrive in social insect colonies as the hosts engage in frequent social interactions, are closely related and live in a pathogen-rich environment, disease outbreaks are rare. This is because social insects have evolved mechanisms to keep pathogens at bay – and fight disease as a collective. Social insect colonies are often viewed as “superorganisms” with division of labor between reproductive “germ-like” queens and males and “somatic” workers, which together form an interdependent reproductive unit that parallels a multicellular body. Superorganisms possess a “social immune system” that comprises of collective disease defenses performed by the workers - summarized as “social immunity”. In social groups immunization (reduced susceptibility to a parasite upon secondary exposure to the same parasite) can e.g. be triggered by social interactions (“social immunization”). Social immunization can be caused by (i) asymptomatic low-level infections that are acquired during caregiving to a contagious individual that can give an immune boost, which can induce protection upon later encounter with the same pathogen (active immunization) or (ii) by transfer of immune effectors between individuals (passive immunization). In the second chapter, I built up on a study that I co-authored that found that low-level infections can not only be protective, but also be costly and make the host more susceptible to detrimental superinfections after contact to a very dissimilar pathogen. I here now tested different degrees of phylogenetically-distant fungal strains of M. brunneum and M. robertsii in L. neglectus and can describe the occurrence of cross-protection of social immunization if the first and second pathogen are from the same level. Interestingly, low-level infections only provided protection when the first strain was less virulent than the second strain and elicited higher immune gene expression. In the third and fourth chapters, I expanded on the role of social immunity in sexual selection, a so far unstudied field. I used the fungus Metarhizium robertsii and the ant Cardiocondyla obscurior as a model, as in this species mating occurs in the presence of workers and can be studied under laboratory conditions. Before males mate with virgin queens in the nest they engage in fierce combat over the access to their mating partners. First, I focused on male-male competition in the third chapter and found that fighting with a contagious male is costly as it can lead to contamination of the rival, but that workers can decrease the risk of disease contraction by performing sanitary care. In the fourth chapter, I studied the effect of fungal infection on survival and mating success of sexuals (freshly emerged queens and males) and found that worker-performed sanitary care can buffer the negative effect that a pathogenic contagion would have on sexuals by spore removal from the exposed individuals. When social immunity was prevented and queens could contract spores from their mating partner, very low dosages led to negative consequences: their lifespan was reduced and they produced fewer offspring with poor immunocompetence compared to healthy queens. Interestingly, cohabitation with a late-stage infected male where no spore transfer was possible had a positive effect on offspring immunity – male offspring of mothers that apparently perceived an infected partner in their vicinity reacted more sensitively to fungal challenge than male offspring without paternal pathogen history.

Modulation of auxin transport via ZF proteins adjust plant response to high ambient temperature - Artner, Christina
As the overall global mean surface temperature is increasing due to climate change, plant adaptation to those stressful conditions is of utmost importance for their survival. Plants are sessile organisms, thus to compensate for their lack of mobility, they evolved a variety of mechanisms enabling them to flexibly adjust their physiological, growth and developmental processes to fluctuating temperatures and to survive in harsh environments. While these unique adaptation abilities provide an important evolutionary advantage, overall modulation of plant growth and developmental program due to non-optimal temperature negatively affects biomass production, crop productivity or sensitivity to pathogens. Thus, understanding molecular processes underlying plant adaptation to increased temperature can provide important resources for breeding strategies to ensure sufficient agricultural food production. An increase in ambient temperature by a few degrees leads to profound changes in organ growth including enhanced hypocotyl elongation, expansion of petioles, hyponastic growth of leaves and cotyledons, collectively named thermomorphogenesis (Casal & Balasubramanian, 2019). Auxin, one of the best-studied growth hormones, plays an essential role in this process by direct activation of transcriptional and non-transcriptional processes resulting in elongation growth (Majda & Robert, 2018).To modulate hypocotyl growth in response to high ambient temperature (hAT), auxin needs to be redistributed accordingly. PINs, auxin efflux transporters, are key components of the polar auxin transport (PAT) machinery, which controls the amount and direction of auxin translocated in the plant tissues and organs(Adamowski & Friml, 2015). Hence, PIN-mediated transport is tightly linked with thermo-morphogenesis, and interference with PAT through either chemical or genetic means dramatically affecting the adaptive responses to hAT. Intriguingly, despite the key role of PIN mediated transport in growth response to hAT, whether and how PINs at the level of expression adapt to fluctuation in temperature is scarcely understood. With genetic, molecular and advanced bio-imaging approaches, we demonstrate the role of PIN auxin transporters in the regulation of hypocotyl growth in response to hAT. We show that via adjustment of PIN3, PIN4 and PIN7 expression in cotyledons and hypocotyls, auxin distribution is modulated thereby determining elongation pattern of epidermal cells at hAT. Furthermore, we identified three Zinc-Finger (ZF) transcription factors as novel molecular components of the thermo-regulatory network, which through negative regulation of PIN transcription adjust the transport of auxin at hAT. Our results suggest that the ZF-PIN module might be a part of the negative feedback loop attenuating the activity of the thermo-sensing pathway to restrain exaggerated growth and developmental responses to hAT.
Keywords: high ambient temperature; auxin; PINs; Zinc-Finger proteins; thermomorphogenesis; stress

Contextual fear learning induced changes in AMPA receptor subtypes along the proximodistal axis in dorsal hippocampus - Jevtic, Marijo
AMPA receptors (AMPARs) mediate fast excitatory neurotransmission and their role is implicated in complex processes such as learning and memory and various neurological diseases. These receptors are composed of different subunits and the subunit composition can affect channel properties, receptor trafficking and interaction with other associated proteins. Using the high sensitivity SDS-digested freeze-fracture replica labeling (SDS-FRL) for electron microscopy I investigated the number, density, and localization of AMPAR subunits, GluA1, GluA2, GluA3, and GluA1-3 (panAMPA) in pyramidal cells in the CA1 area of mouse hippocampus. I have found that the immunogold labeling for all of these subunits in the postsynaptic sites was highest in stratum radiatum and lowest in stratum lacunosummoleculare. The labeling density for the all subunits in the extrasynaptic sites showed a gradual increase from the pyramidal cell soma towards the distal part of stratum radiatum. The densities of extrasynaptic GluA1, GluA2 and panAMPA labeling reached 10-15% of synaptic densities, while the ratio of extrasynaptic labeling for GluA3 was significantly lower compared than those for other subunits. The labeling patterns for GluA1, GluA2 and GluA1-3 are similar and their densities were higher in the periphery than center of synapses. In contrast, the GluA3- containing receptors were more centrally localized compared to the GluA1- and GluA2- containing receptors. The hippocampus plays a central role in learning and memory. Contextual learning has been shown to require the delivery of AMPA receptors to CA1 synapses in the dorsal hippocampus. However, proximodistal heterogeneity of this plasticity and particular contribution of different AMPA receptor subunits are not fully understood. By combining inhibitory avoidance task, a hippocampus-dependent contextual fear-learning paradigm, with SDS-FRL, I have revealed an increase in synaptic density specific to GluA1-containing AMPA receptors in the CA1 area. The intrasynaptic distribution of GluA1 also changed from the periphery to center-preferred pattern. Furthermore, this synaptic plasticity was evident selectively in stratum radiatum but not stratum oriens, and in the CA1 subregion proximal but not distal to CA2. These findings further contribute to our understanding of how specific hippocampal subregions and AMPA receptor subunits are involved in physiological learning. Although the immunolabeling results above shed light on subunit-specific plasticity in AMPAR distribution, no tools to visualize and study the subunit composition at the single channel level in situ have been available. Electron microscopy with conventional immunogold labeling approaches has limitations in the single channel analysis because of the large size of antibodies and steric hindrance hampering multiple subunit labeling of single channels. I managed to develop a new chemical labeling system using a short peptide tag and small synthetic probes, which form specific covalent bond with a cysteine residue in the tag fused to proteins of interest (reactive tag system). I additionally made substantial progress into adapting this system for AMPA receptor subunits.

A universal coupling mechanism of respiratory complex I - Kravchuk, Vladyslav; Petrova, Olga; Kampjut, Domen; Wojciechowska-Bason, Anna; Breese, Zara; Sazanov, Leonid A (Nature)
Complex I is the first enzyme in the respiratory chain, which is responsible for energy production in mitochondria and bacteria1. Complex I couples the transfer of two electrons from NADH to quinone and the translocation of four protons across the membrane2, but the coupling mechanism remains contentious. Here we present cryo-electron microscopy structures of Escherichia coli complex I (EcCI) in different redox states, including catalytic turnover. EcCI exists mostly in the open state, in which the quinone cavity is exposed to the cytosol, allowing access for water molecules, which enable quinone movements. Unlike the mammalian paralogues3, EcCI can convert to the closed state only during turnover, showing that closed and open states are genuine turnover intermediates. The open-to-closed transition results in the tightly engulfed quinone cavity being connected to the central axis of the membrane arm, a source of substrate protons. Consistently, the proportion of the closed state increases with increasing pH. We propose a detailed but straightforward and robust mechanism comprising a ‘domino effect’ series of proton transfers and electrostatic interactions: the forward wave (‘dominoes stacking’) primes the pump, and the reverse wave (‘dominoes falling’) results in the ejection of all pumped protons from the distal subunit NuoL. This mechanism explains why protons exit exclusively from the NuoL subunit and is supported by our mutagenesis data. We contend that this is a universal coupling mechanism of complex I and related enzymes.
Keywords: Multidisciplinary

Controllable states of superconducting Qubit ensembles - Redchenko, Elena
Recent substantial advances in the feld of superconducting circuits have shown its potential as a leading platform for future quantum computing. In contrast to classical computers based on bits that are represented by a single binary value, 0 or 1, quantum bits (or qubits) can be in a superposition of both. Thus, quantum computers can store and handle more information at the same time and a quantum advantage has already been demonstrated for two types of computational tasks. Rapid progress in academic and industry labs accelerates the development of superconducting processors which may soon fnd applications in complex computations, chemical simulations, cryptography, and optimization. Now that these machines are scaled up to tackle such problems the questions of qubit interconnects and networks becomes very relevant. How to route signals on-chip between diferent processor components? What is the most efcient way to entangle qubits? And how to then send and process entangled signals between distant cryostats hosting superconducting processors? In this thesis, we are looking for solutions to these problems by studying the collective behavior of superconducting qubit ensembles. We frst demonstrate on-demand tunable directional scattering of microwave photons from a pair of qubits in a waveguide. Such a device can route microwave photons on-chip with a high diode efciency. Then we focus on studying ultra-strong coupling regimes between light (microwave photons) and matter (superconducting qubits), a regime that could be promising for extremely fast multi-qubit entanglement generation. Finally, we show coherent pulse storage and periodic revivals in a fve qubit ensemble strongly coupled to a resonator. Such a reconfgurable storage device could be used as part of a quantum repeater that is needed for longer-distance quantum communication. The achieved high degree of control over multi-qubit ensembles highlights not only the beautiful physics of circuit quantum electrodynamics, it also represents the frst step toward new quantum simulation and communication methods, and certain techniques may also fnd applications in future superconducting quantum computing hardware.

On the encoding, transfer, and consolidation of spatial memories - Nardin, Michele
The ability to form and retrieve memories is central to survival. In mammals, the hippocampus is a brain region essential to the acquisition and consolidation of new memories. It is also involved in keeping track of one’s position in space and aids navigation. Although this space-memory has been a source of contradiction, evidence supports the view that the role of the hippocampus in navigation is memory, thanks to the formation of cognitive maps. First introduced by Tolman in 1948, cognitive maps are generally used to organize experiences in memory; however, the detailed mechanisms by which these maps are formed and stored are not yet agreed upon. Some influential theories describe this process as involving three fundamental steps: initial encoding by the hippocampus, interactions between the hippocampus and other cortical areas, and long-term extra-hippocampal consolidation. In this thesis, I will show how the investigation of cognitive maps of space helped to shed light on each of these three memory processes. The first study included in this thesis deals with the initial encoding of spatial memories in the hippocampus. Much is known about encoding at the level of single cells, but less about their co-activity or joint contribution to the encoding of novel spatial information. I will describe the structure of an interaction network that allows for efficient encoding of noisy spatial information during the first exploration of a novel environment. The second study describes the interactions between the hippocampus and the prefrontal cortex (PFC), two areas directly and indirectly connected. It is known that the PFC, in concert with the hippocampus, is involved in various processes, including memory storage and spatial navigation. Nonetheless, the detailed mechanisms by which PFC receives information from the hippocampus are not clear. I will show how a transient improvement in theta phase locking of PFC cells enables interactions of cell pairs across the two regions. The third study describes the learning of behaviorally-relevant spatial locations in the hippocampus and the medial entorhinal cortex. I will show how the accumulation of firing around goal locations, a correlate of learning, can shed light on the transition from short- to long-term spatial memories and the speed of consolidation in different brain areas. The studies included in this thesis represent the main scientific contributions of my Ph.D. They involve statistical analyses and models of neural responses of cells in different brain areas of rats executing spatial tasks. I will conclude the thesis by discussing the impact of the findings on principles of memory formation and retention, including the mechanisms, the speed, and the duration of these processes.

A tool for mapping microglial morphology, morphOMICs, reveals brain-region and sex-dependent phenotypes - Colombo, Gloria; Cubero, Ryan J; Kanari, Lida; Venturino, Alessandro; Schulz, Rouven; Scolamiero, Martina; Agerberg, Jens; Mathys, Hansruedi; Tsai, Li-Huei; Chachólski, Wojciech; Hess, Kathryn; Siegert, Sandra (Nature Neuroscience)
Environmental cues influence the highly dynamic morphology of microglia. Strategies to characterize these changes usually involve user-selected morphometric features, which preclude the identification of a spectrum of context-dependent morphological phenotypes. Here we develop MorphOMICs, a topological data analysis approach, which enables semiautomatic mapping of microglial morphology into an atlas of cue-dependent phenotypes and overcomes feature-selection biases and biological variability. We extract spatially heterogeneous and sexually dimorphic morphological phenotypes for seven adult mouse brain regions. This sex-specific phenotype declines with maturation but increases over the disease trajectories in two neurodegeneration mouse models, with females showing a faster morphological shift in affected brain regions. Remarkably, microglia morphologies reflect an adaptation upon repeated exposure to ketamine anesthesia and do not recover to control morphologies. Finally, we demonstrate that both long primary processes and short terminal processes provide distinct insights to morphological phenotypes. MorphOMICs opens a new perspective to characterize microglial morphology.
Keywords: General Neuroscience

MorphOMICs, a tool for mapping microglial morphology, reveals brain region- and sex-dependent phenotypes - Colombo, Gloria
Environmental cues influence the highly dynamic morphology of microglia. Strategies to characterize these changes usually involve user-selected morphometric features, which preclude the identification of a spectrum of context-dependent morphological phenotypes. Here, we develop MorphOMICs, a topological data analysis approach, which enables semiautomatic mapping of microglial morphology into an atlas of cue-dependent phenotypes, overcomes feature-selection bias and minimizes biological variability. First, with MorphOMICs we derive the morphological spectrum of microglia across seven brain regions during postnatal development and in two distinct Alzheimer’s disease degeneration mouse models. We uncover region-specific and sexually dimorphic morphological trajectories, with females showing an earlier morphological shift than males in the degenerating brain. Overall, we demonstrate that both long primary- and short terminal processes provide distinct insights to morphological phenotypes. Moreover, using machine learning to map novel condition on the spectrum, we observe that microglia morphologies reflect a dose-dependent adaptation upon ketamine anesthesia and do not recover to control morphologies. Next, we took advantage of MorphOMICs to build a high-resolution and layer-specific map of microglial morphological spectrum in the retina, covering postnatal development and rd10 degeneration. Here, following photoreceptor death, microglia assume an early developmentlike morphology. Finally, we map microglial morphology following optic nerve crush on the retinal spectrum and observe a layer- and sex-dependent response. Overall, MorphOMICs opens a new perspective to analyze microglial morphology across multiple conditions, and provides a novel tool to characterize microglial morphology beyond the traditionally dichotomized view of microglia.

A context-aware dimension reduction framework for trajectory and health signal analyses - Goudarzi, Samira; Sharif, Mohammad; Karimipour, Farid (Journal of Ambient Intelligence and Humanized Computing)
It is practical to collect a huge amount of movement data and environmental context information along with the health signals of individuals because there is the emergence of new generations of positioning and tracking technologies and rapid advancements of health sensors. The study of the relations between these datasets and their sequence similarity analysis is of interest to many applications such as health monitoring and recommender systems. However, entering all movement parameters and health signals can lead to the complexity of the problem and an increase in its computational load. In this situation, dimension reduction techniques can be used to avoid consideration of simultaneous dependent parameters in the process of similarity measurement of the trajectories. The present study provides a framework, named CaDRAW, to use spatial–temporal data and movement parameters along with independent context information in the process of measuring the similarity of trajectories. In this regard, the omission of dependent movement characteristic signals is conducted by using an unsupervised feature selection dimension reduction technique. To evaluate the effectiveness of the proposed framework, it was applied to a real contextualized movement and related health signal datasets of individuals. The results indicated the capability of the proposed framework in measuring the similarity and in decreasing the characteristic signals in such a way that the similarity results -before and after reduction of dependent characteristic signals- have small differences. The mean differences between the obtained results before and after reducing the dimension were 0.029 and 0.023 for the round path, respectively.
Keywords: general computer science

The genetic basis of complex traits studied via analysis of evolve and resequence experiments - Belohlavy, Stefanie
In evolve and resequence experiments, a population is sequenced, subjected to selection and then sequenced again, so that genetic changes before and after selection can be observed at the genetic level. Here, I use these studies to better understand the genetic basis of complex traits - traits which depend on more than a few genes. In the first chapter, I discuss the first evolve and resequence experiment, in which a population of mice, the so-called "Longshanks" mice, were selected for tibia length while their body mass was kept constant. The full pedigree is known. We observed a selection response on all chromosomes and used the infinitesimal model with linkage, a model which assumes an infinite number of genes with infinitesimally small effect sizes, as a null model. Results implied a very polygenic basis with a few loci of major effect standing out and changing in parallel. There was large variability between the different chromosomes in this study, probably due to LD. In chapter two, I go on to discuss the impact of LD, on the variability in an allele-frequency based summary statistic, giving an equation based on the initial allele frequencies, average pairwise LD, and the first four moments of the haplotype block copy number distribution. I describe this distribution by referring back to the founder generation. I then demonstrate how to infer selection via a maximum likelihood scheme on the example of a single locus and discuss how to extend this to more realistic scenarios. In chapter three, I discuss the second evolve and resequence experiment, in which a small population of Drosophila melanogaster was selected for increased pupal case size over 6 generations. The experiment was highly replicated with 27 lines selected within family and a known pedigree. We observed a phenotypic selection response of over one standard deviation. I describe the patterns in allele frequency data, including allele frequency changes and patterns of heterozygosity, and give ideas for future work.

WASp triggers mechanosensitive actin patches to facilitate immune cell migration in dense tissues - Gaertner, Florian; Reis-Rodrigues, Patricia; De Vries, Ingrid; Hons, Miroslav; Aguilera, Juan; Riedl, Michael; Leithner, Alexander F; Tasciyan, Saren; Kopf, Aglaja; Merrin, Jack; Zheden, Vanessa; Kaufmann, Walter; et al. (Developmental Cell)
When crawling through the body, leukocytes often traverse tissues that are densely packed with extracellular matrix and other cells, and this raises the question: How do leukocytes overcome compressive mechanical loads? Here, we show that the actin cortex of leukocytes is mechanoresponsive and that this responsiveness requires neither force sensing via the nucleus nor adhesive interactions with a substrate. Upon global compression of the cell body as well as local indentation of the plasma membrane, Wiskott-Aldrich syndrome protein (WASp) assembles into dot-like structures, providing activation platforms for Arp2/3 nucleated actin patches. These patches locally push against the external load, which can be obstructing collagen fibers or other cells, and thereby create space to facilitate forward locomotion. We show in vitro and in vivo that this WASp function is rate limiting for ameboid leukocyte migration in dense but not in loose environments and is required for trafficking through diverse tissues such as skin and lymph nodes.

Role of microenvironment heterogeneity in cancer cell invasion - Tasciyan, Saren
Detachment of the cancer cells from the bulk of the tumor is the first step of metastasis, which is the primary cause of cancer related deaths. It is unclear, which factors contribute to this step. Recent studies indicate a crucial role of the tumor microenvironment in malignant transformation and metastasis. Studying cancer cell invasion and detachments quantitatively in the context of its physiological microenvironment is technically challenging. Especially, precise control of microenvironmental properties in vivo is currently not possible. Here, I studied the role of microenvironment geometry in the invasion and detachment of cancer cells from the bulk with a simplistic and reductionist approach. In this approach, I engineered microfluidic devices to mimic a pseudo 3D extracellular matrix environment, where I was able to quantitatively tune the geometrical configuration of the microenvironment and follow tumor cells with fluorescence live imaging. To aid quantitative analysis I developed a widely applicable software application to automatically analyze and visualize particle tracking data. Quantitative analysis of tumor cell invasion in isotropic and anisotropic microenvironments showed that heterogeneity in the microenvironment promotes faster invasion and more frequent detachment of cells. These observations correlated with overall higher speed of cells at the edge of the bulk of the cells. In heterogeneous microenvironments cells preferentially passed through larger pores, thus invading areas of least resistance and generating finger-like invasive structures. The detachments occurred mostly at the tips of these structures. To investigate the potential mechanism, we established a two dimensional model to simulate active Brownian particles representing the cell nuclei dynamics. These simulations backed our in vitro observations without the need of precise fitting the simulation parameters. Our model suggests the importance of the pore heterogeneity in the direction perpendicular to the orientation of bias field (lateral heterogeneity), which causes the interface roughening.

Eps15/Pan1p is a master regulator of the late stages of the endocytic pathway - Enshoji, Mariko; Miyano, Yoshiko; Yoshida, Nao; Nagano, Makoto; Watanabe, Minami; Kunihiro, Mayumi; Siekhaus, Daria E; Toshima, Junko Y.; Toshima, Jiro (Journal of Cell Biology)
Endocytosis is a multistep process involving the sequential recruitment and action of numerous proteins. This process can be divided into two phases: an early phase, in which sites of endocytosis are formed, and a late phase in which clathrin-coated vesicles are formed and internalized into the cytosol, but how these phases link to each other remains unclear. In this study, we demonstrate that anchoring the yeast Eps15-like protein Pan1p to the peroxisome triggers most of the events occurring during the late phase at the peroxisome. At this ectopic location, Pan1p recruits most proteins that function in the late phases—including actin nucleation promoting factors—and then initiates actin polymerization. Pan1p also recruited Prk1 kinase and actin depolymerizing factors, thereby triggering disassembly immediately after actin assembly and inducing dissociation of endocytic proteins from the peroxisome. These observations suggest that Pan1p is a key regulator for initiating, processing, and completing the late phase of endocytosis.

Fos regulates macrophage infiltration against surrounding tissue resistance by a cortical actin-based mechanism in Drosophila - Belyaeva, Vera; Wachner, Stephanie; György, Attila; Emtenani, Shamsi; Gridchyn, Igor; Akhmanova, Maria; Linder, M; Roblek, Marko; Sibilia, M; Siekhaus, Daria E (PLoS Biology)
The infiltration of immune cells into tissues underlies the establishment of tissue-resident macrophages and responses to infections and tumors. Yet the mechanisms immune cells utilize to negotiate tissue barriers in living organisms are not well understood, and a role for cortical actin has not been examined. Here, we find that the tissue invasion of Drosophila macrophages, also known as plasmatocytes or hemocytes, utilizes enhanced cortical F-actin levels stimulated by the Drosophila member of the fos proto oncogene transcription factor family (Dfos, Kayak). RNA sequencing analysis and live imaging show that Dfos enhances F-actin levels around the entire macrophage surface by increasing mRNA levels of the membrane spanning molecular scaffold tetraspanin TM4SF, and the actin cross-linking filamin Cheerio, which are themselves required for invasion. Both the filamin and the tetraspanin enhance the cortical activity of Rho1 and the formin Diaphanous and thus the assembly of cortical actin, which is a critical function since expressing a dominant active form of Diaphanous can rescue the Dfos macrophage invasion defect. In vivo imaging shows that Dfos enhances the efficiency of the initial phases of macrophage tissue entry. Genetic evidence argues that this Dfos-induced program in macrophages counteracts the constraint produced by the tension of surrounding tissues and buffers the properties of the macrophage nucleus from affecting tissue entry. We thus identify strengthening the cortical actin cytoskeleton through Dfos as a key process allowing efficient forward movement of an immune cell into surrounding tissues.

Transcriptional regulation by Dfos and BMP-signaling support tissue invasion of Drosophila immune cells - Wachner, Stephanie
The infiltration of immune cells into tissues underlies the establishment of tissue-resident macrophages and responses to infections and tumors. However, the mechanisms immune cells utilize to collectively migrate through tissue barriers in vivo are not yet well understood. In this thesis, I describe two mechanisms that Drosophila immune cells (hemocytes) use to overcome the tissue barrier of the germband in the embryo. One strategy is the strengthening of the actin cortex through developmentally controlled transcriptional regulation induced by the Drosophila proto-oncogene family member Dfos, which I show in Chapter 2. Dfos induces expression of the tetraspanin TM4SF and the filamin Cher leading to higher levels of the activated formin Dia at the cortex and increased cortical F-actin. This enhanced cortical strength allows hemocytes to overcome the physical resistance of the surrounding tissue and translocate their nucleus to move forward. This mechanism affects the speed of migration when hemocytes face a confined environment in vivo. Another aspect of the invasion process is the initial step of the leading hemocytes entering the tissue, which potentially guides the follower cells. In Chapter 3, I describe a novel subpopulation of hemocytes activated by BMP signaling prior to tissue invasion that leads penetration into the germband. Hemocytes that are deficient in BMP signaling activation show impaired persistence at the tissue entry, while their migration speed remains unaffected. This suggests that there might be different mechanisms controlling immune cell migration within the confined environment in vivo, one of these being the general ability to overcome the resistance of the surrounding tissue and another affecting the order of hemocytes that collectively invade the tissue in a stream of individual cells. Together, my findings provide deeper insights into transcriptional changes in immune cells that enable efficient tissue invasion and pave the way for future studies investigating the early colonization of tissues by macrophages in higher organisms. Moreover, they extend the current view of Drosophila immune cell heterogeneity and point toward a potentially conserved role for canonical BMP signaling in specifying immune cells that lead the migration of tissue resident macrophages during embryogenesis.

CHD8 haploinsufficiency links autism to transient alterations in excitatory and inhibitory trajectories - Villa, Carlo Emanuele; Cheroni, Cristina; Dotter, Christoph; López-Tóbon, Alejandro; Oliveira, Bárbara; Sacco, Roberto; Yahya, Aysan Çerağ; Morandell, Jasmin; Gabriele, Michele; Tavakoli, Mojtaba; Lyudchik, Julia; Sommer, Christoph M; et al. (Cell Reports)
Mutations in the chromodomain helicase DNA-binding 8 (CHD8) gene are a frequent cause of autism spectrum disorder (ASD). While its phenotypic spectrum often encompasses macrocephaly, implicating cortical abnormalities, how CHD8 haploinsufficiency affects neurodevelopmental is unclear. Here, employing human cerebral organoids, we find that CHD8 haploinsufficiency disrupted neurodevelopmental trajectories with an accelerated and delayed generation of, respectively, inhibitory and excitatory neurons that yields, at days 60 and 120, symmetrically opposite expansions in their proportions. This imbalance is consistent with an enlargement of cerebral organoids as an in vitro correlate of patients’ macrocephaly. Through an isogenic design of patient-specific mutations and mosaic organoids, we define genotype-phenotype relationships and uncover their cell-autonomous nature. Our results define cell-type-specific CHD8-dependent molecular defects related to an abnormal program of proliferation and alternative splicing. By identifying cell-type-specific effects of CHD8 mutations, our study uncovers reproducible developmental alterations that may be employed for neurodevelopmental disease modeling.
Keywords: General Biochemistry; Genetics and Molecular Biology

Transcriptional consequences of mutations in genes associated with Autism Spectrum Disorder - Dotter, Christoph
Autism spectrum disorders (ASDs) are a group of neurodevelopmental disorders characterized by behavioral symptoms such as problems in social communication and interaction, as well as repetitive, restricted behaviors and interests. These disorders show a high degree of heritability and hundreds of risk genes have been identifed using high throughput sequencing technologies. This genetic heterogeneity has hampered eforts in understanding the pathogenesis of ASD but at the same time given rise to the concept of convergent mechanisms. Previous studies have identifed that risk genes for ASD broadly converge onto specifc functional categories with transcriptional regulation being one of the biggest groups. In this thesis, I focus on this subgroup of genes and investigate the gene regulatory consequences of some of them in the context of neurodevelopment. First, we showed that mutations in the ASD and intellectual disability risk gene Setd5 lead to perturbations of gene regulatory programs in early cell fate specifcation. In addition, adult animals display abnormal learning behavior which is mirrored at the transcriptional level by altered activity dependent regulation of postsynaptic gene expression. Lastly, we link the regulatory function of Setd5 to its interaction with the Paf1 and the NCoR complex. Second, by modeling the heterozygous loss of the top ASD gene CHD8 in human cerebral organoids we demonstrate profound changes in the developmental trajectories of both inhibitory and excitatory neurons using single cell RNA-sequencing. While the former were generated earlier in CHD8+/- organoids, the generation of the latter was shifted to later times in favor of a prolonged progenitor expansion phase and ultimately increased organoid size. Finally, by modeling heterozygous mutations for four ASD associated chromatin modifers, ASH1L, KDM6B, KMT5B, and SETD5 in human cortical spheroids we show evidence of regulatory convergence across three of those genes. We observe a shift from dorsal cortical excitatory neuron fates towards partially ventralized cell types resembling cells from the lateral ganglionic eminence. As this project is still ongoing at the time of writing, future experiments will aim at elucidating the regulatory mechanisms underlying this shift with the aim of linking these three ASD risk genes through biological convergence.

ZW sex-chromosome evolution and contagious parthenogenesis in Artemia brine shrimp - Elkrewi, Marwan N; Khauratovich, Uladzislava; Toups, Melissa A; Bett, Vincent K; Mrnjavac, Andrea; Macon, Ariana; Fraisse, Christelle; Sax, Luca; Huylmans, Ann K; Hontoria, Francisco; Vicoso, Beatriz (Genetics)
Eurasian brine shrimp (genus Artemia) have closely related sexual and asexual lineages of parthenogenetic females, which produce rare males at low frequencies. Although they are known to have ZW chromosomes, these are not well characterized, and it is unclear whether they are shared across the clade. Furthermore, the underlying genetic architecture of the transmission of asexuality, which can occur when rare males mate with closely related sexual females, is not well understood. We produced a chromosome-level assembly for the sexual Eurasian species Artemia sinica and characterized in detail the pair of sex chromosomes of this species. We combined this new assembly with short-read genomic data for the sexual species Artemia sp. Kazakhstan and several asexual lineages of Artemia parthenogenetica, allowing us to perform an in-depth characterization of sex-chromosome evolution across the genus. We identified a small differentiated region of the ZW pair that is shared by all sexual and asexual lineages, supporting the shared ancestry of the sex chromosomes. We also inferred that recombination suppression has spread to larger sections of the chromosome independently in the American and Eurasian lineages. Finally, we took advantage of a rare male, which we backcrossed to sexual females, to explore the genetic basis of asexuality. Our results suggest that parthenogenesis is likely partly controlled by a locus on the Z chromosome, highlighting the interplay between sex determination and asexuality.
Keywords: Genetics

Data from Elkrewi, Khauratovich, Toups et al. 2022, "ZW sex-chromosome evolution and contagious parthenogenesis in Artemia brine shrimp" - Elkrewi, Marwan N
Eurasian brine shrimp (genus Artemia) have closely related sexual and asexual lineages of parthenogenetic females, which produce rare males at low frequencies. Although they are known to have ZW chromosomes, these are not well characterized, and it is unclear whether they are shared across the clade. Furthermore, the underlying genetic architecture of the transmission of asexuality, which can occur when rare males mate with closely related sexual females, is not well understood. We produced a chromosome-level assembly for the sexual Eurasian species A. sinica and characterized in detail the pair of sex chromosomes of this species. We combined this new assembly with short-read genomic data for the sexual species A. sp. Kazakhstan and several asexual lineages of A. parthenogenetica, allowing us to perform an in-depth characterization of sex-chromosome evolution across the genus. We identified a small differentiated region of the ZW pair that is shared by all sexual and asexual lineages, supporting the shared ancestry of the sex chromosomes. We also inferred that recombination suppression has spread to larger sections of the chromosome independently in the American and Eurasian lineages. Finally, we took advantage of a rare male, which we backcrossed to sexual females, to explore the genetic basis of asexuality. Our results suggest that parthenogenesis is likely partly controlled by a locus on the Z chromosome, highlighting the interplay between sex determination and asexuality.

Weak convergence for variational inequalities with inertial-type method - Shehu, Yekini; Iyiola, Olaniyi S. (Applicable Analysis)
Weak convergence of inertial iterative method for solving variational inequalities is the focus of this paper. The cost function is assumed to be non-Lipschitz and monotone. We propose a projection-type method with inertial terms and give weak convergence analysis under appropriate conditions. Some test results are performed and compared with relevant methods in the literature to show the efficiency and advantages given by our proposed methods.

Saturated reconstruction of living brain tissue - Velicky, Philipp; Miguel Villalba, Eder; Michalska, Julia M; Wei, Donglai; Lin, Zudi; Watson, Jake; Troidl, Jakob; Beyer, Johanna; Ben Simon, Yoav; Sommer, Christoph M; Jahr, Wiebke; Cenameri, Alban; et al. (bioRxiv)
Complex wiring between neurons underlies the information-processing network enabling all brain functions, including cognition and memory. For understanding how the network is structured, processes information, and changes over time, comprehensive visualization of the architecture of living brain tissue with its cellular and molecular components would open up major opportunities. However, electron microscopy (EM) provides nanometre-scale resolution required for full in-silico reconstruction 1–5 , yet is limited to fixed specimens and static representations. Light microscopy allows live observation, with super-resolution approaches 6–12 facilitating nanoscale visualization, but comprehensive 3D-reconstruction of living brain tissue has been hindered by tissue photo-burden, photobleaching, insufficient 3D-resolution, and inadequate signal-to-noise ratio (SNR). Here we demonstrate saturated reconstruction of living brain tissue. We developed an integrated imaging and analysis technology, adapting stimulated emission depletion (STED) microscopy 6,13 in extracellularly labelled tissue 14 for high SNR and near-isotropic resolution. Centrally, a two-stage deep-learning approach leveraged previously obtained information on sample structure to drastically reduce photo-burden and enable automated volumetric reconstruction down to single synapse level. Live reconstruction provides unbiased analysis of tissue architecture across time in relation to functional activity and targeted activation, and contextual understanding of molecular labelling. This adoptable technology will facilitate novel insights into the dynamic functional architecture of living brain tissue.

Uncovering brain tissue architecture across scales with super-resolution light microscopy - Michalska, Julia M; Lyudchik, Julia; Velicky, Philipp; Korinkova, Hana; Watson, Jake; Cenameri, Alban; Sommer, Christoph M; Venturino, Alessandro; Roessler, Karl; Czech, Thomas; Siegert, Sandra; Novarino, Gaia; et al. (bioRxiv)
Mapping the complex and dense arrangement of cells and their connectivity in brain tissue demands nanoscale spatial resolution imaging. Super-resolution optical microscopy excels at visualizing specific molecules and individual cells but fails to provide tissue context. Here we developed Comprehensive Analysis of Tissues across Scales (CATS), a technology to densely map brain tissue architecture from millimeter regional to nanoscopic synaptic scales in diverse chemically fixed brain preparations, including rodent and human. CATS leverages fixation-compatible extracellular labeling and advanced optical readout, in particular stimulated-emission depletion and expansion microscopy, to comprehensively delineate cellular structures. It enables 3D-reconstructing single synapses and mapping synaptic connectivity by identification and tailored analysis of putative synaptic cleft regions. Applying CATS to the hippocampal mossy fiber circuitry, we demonstrate its power to reveal the system’s molecularly informed ultrastructure across spatial scales and assess local connectivity by reconstructing and quantifying the synaptic input and output structure of identified neurons.

Trajectorial dissipation and gradient flow for the relative entropy in Markov chains - Karatzas, Ioannis; Maas, Jan; Schachermayer, Walter (Communications in Information and Systems)
We study the temporal dissipation of variance and relative entropy for ergodic Markov Chains in continuous time, and compute explicitly the corresponding dissipation rates. These are identified, as is well known, in the case of the variance in terms of an appropriate Hilbertian norm; and in the case of the relative entropy, in terms of a Dirichlet form which morphs into a version of the familiar Fisher information under conditions of detailed balance. Here we obtain trajectorial versions of these results, valid along almost every path of the random motion and most transparent in the backwards direction of time. Martingale arguments and time reversal play crucial roles, as in the recent work of Karatzas, Schachermayer and Tschiderer for conservative diffusions. Extensions are developed to general “convex divergences” and to countable state-spaces. The steepest descent and gradient flow properties for the variance, the relative entropy, and appropriate generalizations, are studied along with their respective geometries under conditions of detailed balance, leading to a very direct proof for the HWI inequality of Otto and Villani in the present context.
Keywords: Markov Chain; relative entropy; time reversal; steepest descent; gradient flow

Decomposing permutation automata - Jecker, Ismael R; Mazzocchi, Nicolas; Wolf, Petra (32nd International Conference on Concurrency Theory)
A deterministic finite automaton (DFA) 𝒜 is composite if its language L(𝒜) can be decomposed into an intersection ⋂_{i = 1}^k L(𝒜_i) of languages of smaller DFAs. Otherwise, 𝒜 is prime. This notion of primality was introduced by Kupferman and Mosheiff in 2013, and while they proved that we can decide whether a DFA is composite, the precise complexity of this problem is still open, with a doubly-exponential gap between the upper and lower bounds. In this work, we focus on permutation DFAs, i.e., those for which the transition monoid is a group. We provide an NP algorithm to decide whether a permutation DFA is composite, and show that the difficulty of this problem comes from the number of non-accepting states of the instance: we give a fixed-parameter tractable algorithm with the number of rejecting states as the parameter. Moreover, we investigate the class of commutative permutation DFAs. Their structural properties allow us to decide compositionality in NL, and even in LOGSPACE if the alphabet size is fixed. Despite this low complexity, we show that complex behaviors still arise in this class: we provide a family of composite DFAs each requiring polynomially many factors with respect to its size. We also consider the variant of the problem that asks whether a DFA is k-factor composite, that is, decomposable into k smaller DFAs, for some given integer k ∈ ℕ. We show that, for commutative permutation DFAs, restricting the number of factors makes the decision computationally harder, and yields a problem with tight bounds: it is NP-complete. Finally, we show that in general, this problem is in PSPACE, and it is in LOGSPACE for DFAs with a singleton alphabet.

Faster algorithms for bounded liveness in graphs and game graphs - Chatterjee, Krishnendu; Henzinger, Monika H; Kale, Sagar Sudhir; Svozil, Alexander (48th International Colloquium on Automata, Languages, and Programming)
Graphs and games on graphs are fundamental models for the analysis of reactive systems, in particular, for model-checking and the synthesis of reactive systems. The class of ω-regular languages provides a robust specification formalism for the desired properties of reactive systems. In the classical infinitary formulation of the liveness part of an ω-regular specification, a "good" event must happen eventually without any bound between the good events. A stronger notion of liveness is bounded liveness, which requires that good events happen within d transitions. Given a graph or a game graph with n vertices, m edges, and a bounded liveness objective, the previous best-known algorithmic bounds are as follows: (i) O(dm) for graphs, which in the worst-case is O(n³); and (ii) O(n² d²) for games on graphs. Our main contributions improve these long-standing algorithmic bounds. For graphs we present: (i) a randomized algorithm with one-sided error with running time O(n^{2.5} log n) for the bounded liveness objectives; and (ii) a deterministic linear-time algorithm for the complement of bounded liveness objectives. For games on graphs, we present an O(n² d) time algorithm for the bounded liveness objectives.

How to tutorial-a-thon - Adams, Henry; Kourimska, Hana; Heiss, Teresa; Percival, Sarah; Ziegelmeier, Lori (Notices of the American Mathematical Society)

A new notion of commutativity for the algorithmic Lovász Local Lemma - Harris, David G.; Iliopoulos, Fotis; Kolmogorov, Vladimir (Approximation, Randomization, and Combinatorial Optimization. Algorithms and Techniques)
The Lovász Local Lemma (LLL) is a powerful tool in probabilistic combinatorics which can be used to establish the existence of objects that satisfy certain properties. The breakthrough paper of Moser and Tardos and follow-up works revealed that the LLL has intimate connections with a class of stochastic local search algorithms for finding such desirable objects. In particular, it can be seen as a sufficient condition for this type of algorithms to converge fast. Besides conditions for existence of and fast convergence to desirable objects, one may naturally ask further questions regarding properties of these algorithms. For instance, "are they parallelizable?", "how many solutions can they output?", "what is the expected "weight" of a solution?", etc. These questions and more have been answered for a class of LLL-inspired algorithms called commutative. In this paper we introduce a new, very natural and more general notion of commutativity (essentially matrix commutativity) which allows us to show a number of new refined properties of LLL-inspired local search algorithms with significantly simpler proofs.

A bit of nondeterminism makes pushdown automata expressive and succinct - Guha, Shibashis; Jecker, Ismael R; Lehtinen, Karoliina; Zimmermann, Martin (46th International Symposium on Mathematical Foundations of Computer Science)
We study the expressiveness and succinctness of good-for-games pushdown automata (GFG-PDA) over finite words, that is, pushdown automata whose nondeterminism can be resolved based on the run constructed so far, but independently of the remainder of the input word. We prove that GFG-PDA recognise more languages than deterministic PDA (DPDA) but not all context-free languages (CFL). This class is orthogonal to unambiguous CFL. We further show that GFG-PDA can be exponentially more succinct than DPDA, while PDA can be double-exponentially more succinct than GFG-PDA. We also study GFGness in visibly pushdown automata (VPA), which enjoy better closure properties than PDA, and for which we show GFGness to be ExpTime-complete. GFG-VPA can be exponentially more succinct than deterministic VPA, while VPA can be exponentially more succinct than GFG-VPA. Both of these lower bounds are tight. Finally, we study the complexity of resolving nondeterminism in GFG-PDA. Every GFG-PDA has a positional resolver, a function that resolves nondeterminism and that is only dependant on the current configuration. Pushdown transducers are sufficient to implement the resolvers of GFG-VPA, but not those of GFG-PDA. GFG-PDA with finite-state resolvers are determinisable.

The generalized spatial representation in the prefrontal cortex is inherited from the hippocampus - Nardin, Michele; Käfer, Karola; Csicsvari, Jozsef L (bioRxiv)
Hippocampal and neocortical neural activity is modulated by the position of the individual in space. While hippocampal neurons provide the basis for a spatial map, prefrontal cortical neurons generalize over environmental features. Whether these generalized representations result from a bidirectional interaction with, or are mainly derived from hippocampal spatial representations is not known. By examining simultaneously recorded hippocampal and medial prefrontal neurons, we observed that prefrontal spatial representations show a delayed coherence with hippocampal ones. We also identified subpopulations of cells in the hippocampus and medial prefrontal cortex that formed functional cross-area couplings; these resembled the optimal connections predicted by a probabilistic model of spatial information transfer and generalization. Moreover, cross-area couplings were strongest and had the shortest delay preceding spatial decision-making. Our results suggest that generalized spatial coding in the medial prefrontal cortex is inherited from spatial representations in the hippocampus, and that the routing of information can change dynamically with behavioral demands.

Durotaxis of passive nanoparticles on elastic membranes - Palaia, Ivan; Paraschiv, Alexandru; Debets, Vincent; Storm, Cornelis; Šarić, Anđela (ACS Nano)
The transport of macromolecules and nanoscopic particles to a target cellular site is a crucial aspect in many physiological processes. This directional motion is generally controlled via active mechanical and chemical processes. Here we show, by means of molecular dynamics simulations and an analytical theory, that completely passive nanoparticles can exhibit directional motion when embedded in non-uniform mechanical environments. Specifically, we study the motion of a passive nanoparticle adhering to a mechanically non-uniform elastic membrane. We observe a non-monotonic affinity of the particle to the membrane as a function of the membrane’s rigidity, which results in the particle transport. This transport can be both up or down the rigidity gradient, depending on the absolute values of the rigidities that the gradient spans across. We conclude that rigidity gradients can be used to direct average motion of passive macromolecules and nanoparticles on deformable membranes, resulting in the preferential accumulation of the macromolecules in regions of certain mechanical properties.

Physical mechanisms of ESCRT-III-driven cell division in archaea - Harker-Kirschneck, L.; Hafner, A. E.; Yao, T.; Pulschen, A.; Hurtig, F.; Vanhille-Campos, C.; Hryniuk, D.; Culley, S.; Henriques, R.; Baum, B.; Šarić, Anđela (bioRxiv)
Living systems propagate by undergoing rounds of cell growth and division. Cell division is at heart a physical process that requires mechanical forces, usually exerted by protein assemblies. Here we developed the first physical model for the division of archaeal cells, which despite their structural simplicity share machinery and evolutionary origins with eukaryotes. We show how active geometry changes of elastic ESCRT-III filaments, coupled to filament disassembly, are sufficient to efficiently split the cell. We explore how the non-equilibrium processes that govern the filament behaviour impact the resulting cell division. We show how a quantitative comparison between our simulations and dynamic data for ESCRTIII-mediated division in Sulfolobus acidocaldarius, the closest archaeal relative to eukaryotic cells that can currently be cultured in the lab, and reveal the most likely physical mechanism behind its division.

Acute and chronic effects of a light-activated FGF receptor in keratinocytes in vitro and in mice - Rauschendorfer, Theresa; Gurri, Selina; Heggli, Irina; Maddaluno, Luigi; Meyer, Michael; Inglés Prieto, Álvaro; Janovjak, Harald L; Werner, Sabine (Life Science Alliance)
FGFs and their high-affinity receptors (FGFRs) play key roles in development, tissue repair, and disease. Because FGFRs bind overlapping sets of ligands, their individual functions cannot be determined using ligand stimulation. Here, we generated a light-activated FGFR2 variant (OptoR2) to selectively activate signaling by the major FGFR in keratinocytes. Illumination of OptoR2-expressing HEK 293T cells activated FGFR signaling with remarkable temporal precision and promoted cell migration and proliferation. In murine and human keratinocytes, OptoR2 activation rapidly induced the classical FGFR signaling pathways and expression of FGF target genes. Surprisingly, multi-level counter-regulation occurred in keratinocytes in vitro and in transgenic mice in vivo, including OptoR2 down-regulation and loss of responsiveness to light activation. These results demonstrate unexpected cell type-specific limitations of optogenetic FGFRs in long-term in vitro and in vivo settings and highlight the complex consequences of transferring optogenetic cell signaling tools into their relevant cellular contexts.

Transitioning from structural to nominal code with efficient gradual typing - Mühlböck, Fabian; Tate, Ross (Proceedings of the ACM on Programming Languages)
Gradual typing is a principled means for mixing typed and untyped code. But typed and untyped code often exhibit different programming patterns. There is already substantial research investigating gradually giving types to code exhibiting typical untyped patterns, and some research investigating gradually removing types from code exhibiting typical typed patterns. This paper investigates how to extend these established gradual-typing concepts to give formal guarantees not only about how to change types as code evolves but also about how to change such programming patterns as well. In particular, we explore mixing untyped "structural" code with typed "nominal" code in an object-oriented language. But whereas previous work only allowed "nominal" objects to be treated as "structural" objects, we also allow "structural" objects to dynamically acquire certain nominal types, namely interfaces. We present a calculus that supports such "cross-paradigm" code migration and interoperation in a manner satisfying both the static and dynamic gradual guarantees, and demonstrate that the calculus can be implemented efficiently.
Keywords: gradual typing; gradual guarantee; nominal; structural; call tags

Capturing tactile properties of real surfaces for haptic reproduction - Degraen, Donald; Piovarci, Michael; Bickel, Bernd; Kruger, Antonio (34th Annual ACM Symposium)
Tactile feedback of an object’s surface enables us to discern its material properties and affordances. This understanding is used in digital fabrication processes by creating objects with high-resolution surface variations to influence a user’s tactile perception. As the design of such surface haptics commonly relies on knowledge from real-life experiences, it is unclear how to adapt this information for digital design methods. In this work, we investigate replicating the haptics of real materials. Using an existing process for capturing an object’s microgeometry, we digitize and reproduce the stable surface information of a set of 15 fabric samples. In a psychophysical experiment, we evaluate the tactile qualities of our set of original samples and their replicas. From our results, we see that direct reproduction of surface variations is able to influence different psychophysical dimensions of the tactile perception of surface textures. While the fabrication process did not preserve all properties, our approach underlines that replication of surface microgeometries benefits fabrication methods in terms of haptic perception by covering a large range of tactile variations. Moreover, by changing the surface structure of a single fabricated material, its material perception can be influenced. We conclude by proposing strategies for capturing and reproducing digitized textures to better resemble the perceived haptics of the originals.

Quantitative nonlinear homogenization: control of oscillations - Clozeau, Nicolas; Gloria, Antoine (arXiv)
Quantitative stochastic homogenization of linear elliptic operators is by now well-understood. In this contribution we move forward to the nonlinear setting of monotone operators with p-growth. This first work is dedicated to a quantitative two-scale expansion result. Fluctuations will be addressed in companion articles. By treating the range of exponents 2≤p<∞ in dimensions d≤3, we are able to consider genuinely nonlinear elliptic equations and systems such as −∇⋅A(x)(1+|∇u|p−2)∇u=f (with A random, non-necessarily symmetric) for the first time. When going from p=2 to p>2, the main difficulty is to analyze the associated linearized operator, whose coefficients are degenerate, unbounded, and depend on the random input A via the solution of a nonlinear equation. One of our main achievements is the control of this intricate nonlinear dependence, leading to annealed Meyers' estimates for the linearized operator, which are key to the quantitative two-scale expansion result.

Sparsity in deep learning: Pruning and growth for efficient inference and training in neural networks - Hoefler, Torsten; Alistarh, Dan-Adrian; Ben-Nun, Tal; Dryden, Nikoli; Peste, Elena-Alexandra (Journal of Machine Learning Research)
The growing energy and performance costs of deep learning have driven the community to reduce the size of neural networks by selectively pruning components. Similarly to their biological counterparts, sparse networks generalize just as well, sometimes even better than, the original dense networks. Sparsity promises to reduce the memory footprint of regular networks to fit mobile devices, as well as shorten training time for ever growing networks. In this paper, we survey prior work on sparsity in deep learning and provide an extensive tutorial of sparsification for both inference and training. We describe approaches to remove and add elements of neural networks, different training strategies to achieve model sparsity, and mechanisms to exploit sparsity in practice. Our work distills ideas from more than 300 research papers and provides guidance to practitioners who wish to utilize sparsity today, as well as to researchers whose goal is to push the frontier forward. We include the necessary background on mathematical methods in sparsification, describe phenomena such as early structure adaptation, the intricate relations between sparsity and the training process, and show techniques for achieving acceleration on real hardware. We also define a metric of pruned parameter efficiency that could serve as a baseline for comparison of different sparse networks. We close by speculating on how sparsity can improve future workloads and outline major open problems in the field.

Brief announcement: Fast graphical population protocols - Alistarh, Dan-Adrian; Gelashvili, Rati; Rybicki, Joel (35th International Symposium on Distributed Computing)
Let G be a graph on n nodes. In the stochastic population protocol model, a collection of n indistinguishable, resource-limited nodes collectively solve tasks via pairwise interactions. In each interaction, two randomly chosen neighbors first read each other’s states, and then update their local states. A rich line of research has established tight upper and lower bounds on the complexity of fundamental tasks, such as majority and leader election, in this model, when G is a clique. Specifically, in the clique, these tasks can be solved fast, i.e., in n polylog n pairwise interactions, with high probability, using at most polylog n states per node. In this work, we consider the more general setting where G is an arbitrary graph, and present a technique for simulating protocols designed for fully-connected networks in any connected regular graph. Our main result is a simulation that is efficient on many interesting graph families: roughly, the simulation overhead is polylogarithmic in the number of nodes, and quadratic in the conductance of the graph. As an example, this implies that, in any regular graph with conductance φ, both leader election and exact majority can be solved in φ^{-2} ⋅ n polylog n pairwise interactions, with high probability, using at most φ^{-2} ⋅ polylog n states per node. This shows that there are fast and space-efficient population protocols for leader election and exact majority on graphs with good expansion properties.

Lower bounds for shared-memory leader election under bounded write contention - Alistarh, Dan-Adrian; Gelashvili, Rati; Nadiradze, Giorgi (35th International Symposium on Distributed Computing)
This paper gives tight logarithmic lower bounds on the solo step complexity of leader election in an asynchronous shared-memory model with single-writer multi-reader (SWMR) registers, for both deterministic and randomized obstruction-free algorithms. The approach extends to lower bounds for deterministic and randomized obstruction-free algorithms using multi-writer registers under bounded write concurrency, showing a trade-off between the solo step complexity of a leader election algorithm, and the worst-case number of stalls incurred by a processor in an execution.

Brief announcement: Non-blocking dynamic unbounded graphs with worst-case amortized bounds - Chatterjee, Bapi; Peri, Sathya; Sa, Muktikanta (35th International Symposium on Distributed Computing)
This paper reports a new concurrent graph data structure that supports updates of both edges and vertices and queries: Breadth-first search, Single-source shortest-path, and Betweenness centrality. The operations are provably linearizable and non-blocking.

Brief announcement: Sinkless orientation is hard also in the supported LOCAL model - Korhonen, Janne; Paz, Ami; Rybicki, Joel; Schmid, Stefan; Suomela, Jukka (35th International Symposium on Distributed Computing)
We show that any algorithm that solves the sinkless orientation problem in the supported LOCAL model requires Ω(log n) rounds, and this is tight. The supported LOCAL is at least as strong as the usual LOCAL model, and as a corollary this also gives a new, short and elementary proof that shows that the round complexity of the sinkless orientation problem in the deterministic LOCAL model is Ω(log n).

Evaluation of gravitropism in non-seed plants - Zhang, Yuzhou; Li, Lanxin; Friml, Jiří (Plant Gravitropism)
Tropisms are among the most important growth responses for plant adaptation to the surrounding environment. One of the most common tropisms is root gravitropism. Root gravitropism enables the plant to anchor securely to the soil enabling the absorption of water and nutrients. Most of the knowledge related to the plant gravitropism has been acquired from the flowering plants, due to limited research in non-seed plants. Limited research on non-seed plants is due in large part to the lack of standard research methods. Here, we describe the experimental methods to evaluate gravitropism in representative non-seed plant species, including the non-vascular plant moss Physcomitrium patens, the early diverging extant vascular plant lycophyte Selaginella moellendorffii and fern Ceratopteris richardii. In addition, we introduce the methods used for statistical analysis of the root gravitropism in non-seed plant species.

Automated time-lapse imaging and manipulation of cell divisions in Arabidopsis roots by vertical-stage confocal microscopy - Hörmayer, Lukas; Friml, Jiří; Glanc, Matous (Plant Cell Division)
The analysis of dynamic cellular processes such as plant cytokinesis stands and falls with live-cell time-lapse confocal imaging. Conventional approaches to time-lapse imaging of cell division in Arabidopsis root tips are tedious and have low throughput. Here, we describe a protocol for long-term time-lapse simultaneous imaging of multiple root tips on a vertical-stage confocal microscope with automated root tracking. We also provide modifications of the basic protocol to implement this imaging method in the analysis of genetic, pharmacological or laser ablation wounding-mediated experimental manipulations. Our method dramatically improves the efficiency of cell division time-lapse imaging by increasing the throughput, while reducing the person-hour requirements of such experiments.

On eigenvector statistics in the spherical and truncated unitary ensembles - Dubach, Guillaume (Electronic Journal of Probability)
We study the overlaps between right and left eigenvectors for random matrices of the spherical ensemble, as well as truncated unitary ensembles in the regime where half of the matrix at least is truncated. These two integrable models exhibit a form of duality, and the essential steps of our investigation can therefore be performed in parallel. In every case, conditionally on all eigenvalues, diagonal overlaps are shown to be distributed as a product of independent random variables with explicit distributions. This enables us to prove that the scaled diagonal overlaps, conditionally on one eigenvalue, converge in distribution to a heavy-tail limit, namely, the inverse of a γ2 distribution. We also provide formulae for the conditional expectation of diagonal and off-diagonal overlaps, either with respect to one eigenvalue, or with respect to the whole spectrum. These results, analogous to what is known for the complex Ginibre ensemble, can be obtained in these cases thanks to integration techniques inspired from a previous work by Forrester & Krishnapur.

Influence of membrane-cortex linkers on the extrusion of membrane tubes - Paraschiv, Alexandru; Lagny, Thibaut J.; Campos, Christian Vanhille; Coudrier, Evelyne; Bassereau, Patricia; Šarić, Anđela (Biophysical Journal)
The cell membrane is an inhomogeneous system composed of phospholipids, sterols, carbohydrates, and proteins that can be directly attached to underlying cytoskeleton. The protein linkers between the membrane and the cytoskeleton are believed to have a profound effect on the mechanical properties of the cell membrane and its ability to reshape. Here, we investigate the role of membrane-cortex linkers on the extrusion of membrane tubes using computer simulations and experiments. In simulations, we find that the force for tube extrusion has a nonlinear dependence on the density of membrane-cortex attachments: at a range of low and intermediate linker densities, the force is not significantly influenced by the presence of the membrane-cortex attachments and resembles that of the bare membrane. For large concentrations of linkers, however, the force substantially increases compared with the bare membrane. In both cases, the linkers provided membrane tubes with increased stability against coalescence. We then pulled tubes from HEK cells using optical tweezers for varying expression levels of the membrane-cortex attachment protein Ezrin. In line with simulations, we observed that overexpression of Ezrin led to an increased extrusion force, while Ezrin depletion had a negligible effect on the force. Our results shed light on the importance of local protein rearrangements for membrane reshaping at nanoscopic scales.
Keywords: biophysics

Physical modeling of multivalent interactions in the nuclear pore complex - Davis, Luke K.; Šarić, Anđela; Hoogenboom, Bart W.; Zilman, Anton (Biophysical Journal)
In the nuclear pore complex, intrinsically disordered proteins (FG Nups), along with their interactions with more globular proteins called nuclear transport receptors (NTRs), are vital to the selectivity of transport into and out of the cell nucleus. Although such interactions can be modeled at different levels of coarse graining, in vitro experimental data have been quantitatively described by minimal models that describe FG Nups as cohesive homogeneous polymers and NTRs as uniformly cohesive spheres, in which the heterogeneous effects have been smeared out. By definition, these minimal models do not account for the explicit heterogeneities in FG Nup sequences, essentially a string of cohesive and noncohesive polymer units, and at the NTR surface. Here, we develop computational and analytical models that do take into account such heterogeneity in a minimal fashion and compare them with experimental data on single-molecule interactions between FG Nups and NTRs. Overall, we find that the heterogeneous nature of FG Nups and NTRs does play a role in determining equilibrium binding properties but is of much greater significance when it comes to unbinding and binding kinetics. Using our models, we predict how binding equilibria and kinetics depend on the distribution of cohesive blocks in the FG Nup sequences and of the binding pockets at the NTR surface, with multivalency playing a key role. Finally, we observe that single-molecule binding kinetics has a rather minor influence on the diffusion of NTRs in polymer melts consisting of FG-Nup-like sequences.
Keywords: biophysics

PLCγ1 promotes phase separation of T cell signaling components - Zeng, Longhui; Palaia, Ivan; Šarić, Anđela; Su, Xiaolei (Journal of Cell Biology)
The T cell receptor (TCR) pathway receives, processes, and amplifies the signal from pathogenic antigens to the activation of T cells. Although major components in this pathway have been identified, the knowledge on how individual components cooperate to effectively transduce signals remains limited. Phase separation emerges as a biophysical principle in organizing signaling molecules into liquid-like condensates. Here, we report that phospholipase Cγ1 (PLCγ1) promotes phase separation of LAT, a key adaptor protein in the TCR pathway. PLCγ1 directly cross-links LAT through its two SH2 domains. PLCγ1 also protects LAT from dephosphorylation by the phosphatase CD45 and promotes LAT-dependent ERK activation and SLP76 phosphorylation. Intriguingly, a nonmonotonic effect of PLCγ1 on LAT clustering was discovered. Computer simulations, based on patchy particles, revealed how the cluster size is regulated by protein compositions. Together, these results define a critical function of PLCγ1 in promoting phase separation of the LAT complex and TCR signal transduction.
Keywords: cell biology

Modelling the dynamics of vesicle reshaping and scission under osmotic shocks - Vanhille-Campos, Christian; Šarić, Anđela (Soft Matter)
We study the effects of osmotic shocks on lipid vesicles via coarse-grained molecular dynamics simulations by explicitly considering the solute in the system. We find that depending on their nature (hypo- or hypertonic) such shocks can lead to bursting events or engulfing of external material into inner compartments, among other morphology transformations. We characterize the dynamics of these processes and observe a separation of time scales between the osmotic shock absorption and the shape relaxation. Our work consequently provides an insight into the dynamics of compartmentalization in vesicular systems as a result of osmotic shocks, which can be of interest in the context of early proto-cell development and proto-cell compartmentalisation.
Keywords: condensed matter physics; general chemistry

Recognizing multimodal entailment - Ilharco, Cesar; Shirazi, Afsaneh; Gopalan, Arjun; Nagrani, Arsha; Bratanič, Blaž; Bregler, Chris; Liu, Christina; Ferreira, Felipe; Barcik, Gabriek; Ilharco, Gabriel; Osang, Georg F; Bulian, Jannis; et al. (59th Annual Meeting of the Association for Computational Linguistics and the 11th International Joint Conference on Natural Language Processing, Tutorial Abstracts)
How information is created, shared and consumed has changed rapidly in recent decades, in part thanks to new social platforms and technologies on the web. With ever-larger amounts of unstructured and limited labels, organizing and reconciling information from different sources and modalities is a central challenge in machine learning. This cutting-edge tutorial aims to introduce the multimodal entailment task, which can be useful for detecting semantic alignments when a single modality alone does not suffice for a whole content understanding. Starting with a brief overview of natural language processing, computer vision, structured data and neural graph learning, we lay the foundations for the multimodal sections to follow. We then discuss recent multimodal learning literature covering visual, audio and language streams, and explore case studies focusing on tasks which require fine-grained understanding of visual and linguistic semantics question answering, veracity and hatred classification. Finally, we introduce a new dataset for recognizing multimodal entailment, exploring it in a hands-on collaborative section. Overall, this tutorial gives an overview of multimodal learning, introduces a multimodal entailment dataset, and encourages future research in the topic.

Cubic Forms and the Circle Method - Browning, Timothy D
The Hardy–Littlewood circle method was invented over a century ago to study integer solutions to special Diophantine equations, but it has since proven to be one of the most successful all-purpose tools available to number theorists. Not only is it capable of handling remarkably general systems of polynomial equations defined over arbitrary global fields, but it can also shed light on the space of rational curves that lie on algebraic varieties. This book, in which the arithmetic of cubic polynomials takes centre stage, is aimed at bringing beginning graduate students into contact with some of the many facets of the circle method, both classical and modern. This monograph is the winner of the 2021 Ferran Sunyer i Balaguer Prize, a prestigious award for books of expository nature presenting the latest developments in an active area of research in mathematics.